Co-fired glass substrates for high frequency electronic packaging and methods of manufacture

By exposing the rotary phase separation glass substrate to an acid solution and depositing conductive material, forming a porous glass circuit board, the problem of absorption loss of existing glass substrates at high frequency is solved, and glass with low loss tangent and dielectric constant is achieved Circuit board meets the needs of high-frequency electronic packaging.

CN119409420APending Publication Date: 2025-02-11CORNING INC
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202410886209.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-03
Filing Date
2024-07-03
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Existing glass substrates have absorption loss problems in high-frequency electronic packaging, which limits the efficiency of signal transmission. Especially at 10GHz or higher, the loss tangent of existing insulating materials reaches the limit, making it difficult to meet high-frequency requirements.

Method used

A portion of the second phase is removed to form a porous glass substrate by exposing the rotary phase separation glass substrate containing the first phase of SiO2 and the second phase of B2O3 at a temperature in the range of 60°C to 95°C, and a portion of the second phase is removed, forming a porous glass substrate. Conductive material is deposited in multiple holes to form an intermediate circuit board, and finally form a glass circuit board by curing.

Benefits of technology

A glass circuit board with a dielectric constant Dk less than 6.0 and a loss tangent Df less than 0.001 at 10GHz is realized, which significantly reduces the signal absorption loss and meets the technical requirements of high-frequency electronic packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409420A_ABST
    Figure CN119409420A_ABST
Patent Text Reader

Abstract

A method of making a glass article using a phase separated silicate glass comprising a silica-rich first phase and a boron-rich second phase. The phase separation silica glass is etched with an etchant to remove at least a portion of the second phase and obtain a high silica content porous glass article. Through holes may be formed in a porous glass article by first forming holes in the porous glass article and filling the holes with a conductive material. The porous glass article may be heat treated to consolidate the porous glass article, thereby closing pores of the porous glass article and obtaining a consolidated glass article having very low dielectric properties. Various glass compositions that are phase-separated via rotary knotting are disclosed.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority under the Patent Law to U.S. Provisional Application Serial No. 63 / 524,732 filed on July 3, 2023, the contents of which are the basis of this application and are incorporated herein by reference in their entirety. Technical Field

[0003] The present disclosure generally relates to glass substrates for high frequency electronic packaging using glass having at least two different glass phases. Background Art

[0004] Digital technology continues to expand, especially in terms of data connectivity and processing rates. For example, processing rates of around 1 Gigabit per second (Gbits / s) are expanding to rates of tens of Gbits / s. The corresponding electronic device technology required to achieve these data rates may result in signal transmission and reception frequencies of around 1 GHz expanding to approximately 100 GHz.

[0005] As these signal frequencies increase to accommodate increased data processing rates, the specifications and requirements related to absorption losses associated with the dielectric materials used in these devices become more important. While some materials have low loss tangents at frequencies greater than 10 GHz, the processing characteristics of these materials can limit their ability to be manufactured using certain forming processes.

[0006] There are a variety of materials available on the market today for use as insulating layers in printed circuit boards (PCBs). For example, a common glass epoxy laminate used as an insulating layer in PCB applications has a loss tangent of 0.0058 at a signal frequency of 10 GHz. However, as the industry moves to higher and higher signal frequencies, this insulating laminate has a limiting loss tangent. Other laminates have been found that exhibit low loss characteristics at frequencies of 10 GHz or higher, such as fused silica-polymer laminates. However, the mechanical properties of the fused silica and polymer layers limit the use of these laminates in certain processes because the fused silica layer may crack during post-processing.

[0007] Materials such as radome high temperature ceramics, high purity fused silica, sapphire, alumina, and silica may have low loss tangent at frequencies greater than 10 GHz. However, these materials may have such high viscosities at forming temperatures that their ability to be processed using standard sheet forming processes such as slot draw and overflow down draw (e.g., fusion) may be limited. There are also some alkali-free glass and glass-ceramic materials that have low loss tangent at frequencies greater than 10 GHz, examples of which include the B2O3-P2O5-SiO2 (BPS) and MgO-Al2O3-SiO2 (MAS) systems. However, the liquidus viscosities of these systems are generally too low to be suitable for common forming methods. Summary of the invention

[0008] In a first aspect, a method for manufacturing a glass article is disclosed, comprising exposing at least one spinodal phase-separated glass substrate comprising a first phase of mainly SiO2 and a second phase containing B2O3 to an acid solution containing about 5 weight percent (wt%) to about 40 wt% of an acid for a period of time in the range of about 8 hours to about 24 hours at a temperature in the range of about 60°C to about 95°C so as to remove at least a portion of the second phase from the at least one spinodal phase-separated glass substrate and obtain at least one porous glass substrate containing a total SiO2 content greater than about 95 mol%. The method also includes forming a plurality of holes in the at least one porous glass substrate, and depositing a conductive material in the plurality of holes to form an intermediate circuit board comprising a plurality of through holes. The method may also include consolidating the intermediate circuit board to form a glass circuit board. After consolidation, the glass circuit board is composed of amorphous glass. In some embodiments, the step of forming a plurality of holes may be performed before the step of exposing the at least one spinodal phase-separated glass substrate to the acid solution (i.e., before obtaining the porous glass substrate).

[0009] In the second aspect, the acid solution of the first aspect may comprise at least one of HCl, H2SO4, HNO3, HF, or H3PO4.

[0010] In the third aspect, the acid solution of the first aspect or the second aspect may comprise HCl.

[0011] In a fourth aspect, the acid solution of any one of the first to third aspects may comprise about 5 wt % HCl.

[0012] In a fifth aspect, the acid solution of the first aspect may include at least one of citric acid or acetic acid.

[0013] In a sixth aspect, the at least one porous glass substrate of any one of the first to fifth aspects may have an open porosity greater than about 28%.

[0014] In the seventh aspect, the forming of the plurality of holes in any one of the first to sixth aspects may include laser ablation or chemical etching.

[0015] In an eighth aspect, the forming of the plurality of holes of the seventh aspect may include RF-exciting a CO 2 laser.

[0016] In a ninth aspect, the forming of the plurality of holes of any of the seventh aspects may include using a laser operating at an ultraviolet wavelength.

[0017] In the tenth aspect, the first aspect may include, before the consolidation, further depositing a conductive material on the porous glass substrate as a line between a first through-hole among the plurality of through-holes and a second through-hole among the plurality of through-holes.

[0018] In an eleventh aspect, the heat treatment of any one of the first to fifth aspects may further include heat treating the intermediate circuit board at a temperature in a range of about 500° C. to about 700° C. for a time in a range of about 45 minutes to about 75 minutes.

[0019] In the twelfth aspect, the consolidation of any one of the first to fifth aspects may include heating the intermediate circuit board to a consolidation temperature in the range of about 850°C to about 1250°C, such as in the range of about 900°C to about 1100°C, for a time in the range of about 1 hour to about 24 hours.

[0020] In the thirteenth aspect, at least one spinodal phase-separation glass substrate of the first aspect may include a plurality of spinodal phase-separation glass substrates, the exposing produces a plurality of porous glass substrates, the method further comprising forming a plurality of holes in at least a subset of the plurality of porous glass substrates, depositing a conductive material in the plurality of holes of at least the subset of the porous glass substrates to obtain a plurality of intermediate circuit boards, arranging the plurality of porous glass substrates and the plurality of intermediate circuit boards to form a stack, and consolidating the stack to form a glass circuit board.

[0021] In a fourteenth aspect, the stack of the thirteenth aspect may be positioned between a pair of thermally conductive substrates prior to consolidation.

[0022] In the fifteenth aspect, the pair of thermally conductive substrates of the fourteenth aspect may include SiC.

[0023] In a sixteenth aspect, the glass circuit board of any one of the first to fifteenth aspects may comprise greater than about 95 mol % SiO2, less than about 1 mol % Al2O3, and less than about 3 mol % B2O3 on an oxide basis.

[0024] In a seventeenth aspect, the glass circuit board of any one of the first to sixteenth aspects may include one or more alkaline earth oxides (RO) in an amount of less than 0.5 mol % in total, wherein RO is at least one of MgO, CaO, SrO, or BaO.

[0025] In the eighteenth aspect, the glass circuit board according to any one of the first to seventeenth aspects has a dielectric constant D k It may be less than about 6.0 when measured at 10 GHz.

[0026] In the nineteenth aspect, D of the eighteenth aspect k Less than about 4.0 when measured at 10 GHz.

[0027] In the twentieth aspect, the loss tangent D of at least one glass circuit board of any one of the first aspect to the nineteenth aspect is f When measured at 30 GHz, it can be less than about 0.001.

[0028] In the 21st aspect, D of the 20th aspect f When measured at 10 GHz, it can be less than about 0.001.

[0029] In the twenty-second aspect, the spinodal phase-separated glass substrate of the first aspect comprises a total amount of SiO2 of about 59 mol% to about 69 mol%, a total amount of Al2O3 of about 3 mol% to about 13 mol%, a total amount of B2O3 of about 9.8 mol% to about 20 mol%, and one or more alkaline earth oxides (RO) totaling about 3.9 mol% to about 11.5 mol%, wherein RO is selected from MgO, CaO, SrO, and BaO.

[0030] In the twenty-third aspect, the spinodal phase separation glass substrate of the twenty-second aspect may have a B2O3 / (Al2O3+SiO2) ratio in the range of about 0.12 to about 0.3.

[0031] In the twenty-fourth aspect, the spinodal phase-separated glass substrate of the twenty-second aspect may include SiO 2 in a range of about 68.0 mol % to about 69.0 mol %.

[0032] In a twenty-fifth aspect, the spinodal decomposed glass substrate of the first aspect may comprise, on an oxide basis, a total amount of SiO2 of about 57 mol% to about 70 mol%, a total amount of Al2O3 of about 4.7 mol% to about 10.5 mol%, a total amount of B2O3 of about 11.2 mol% to about 15.2 mol%, a total amount of ZnO of about 1.2 mol% to about 7.4 mol%, and one or more alkaline earth oxides (RO) totaling about 3.7 mol% to about 20 mol%, wherein RO is selected from MgO, CaO, SrO, and BaO.

[0033] In the twenty-sixth aspect, the glass of the twenty-fifth aspect can include SnO in a range of about 0.09 mol % to about 0.15 mol %.

[0034] In the twenty-seventh aspect, the spinodal phase-separated glass substrate of the twenty-sixth aspect may include MgO in a range of about 1.5 mol % to about 9.6 mol %.

[0035] In the twenty-eighth aspect, the spinodal phase separation glass substrate of the twenty-seventh aspect may have MgO / ZnO in the range of about 0 to about 3.7.

[0036] In the twenty-ninth aspect, the spinodal phase separation glass substrate of the twenty-seventh aspect may have B2O3 / ZnO in the range of about 1.6 to about 12.6.

[0037] In a thirtieth aspect, a glass circuit board is disclosed, comprising greater than about 95 mol% SiO2, less than about 1 mol% Al2O3, less than about 3 mol% B2O3, a plurality of holes disposed in the glass circuit board, and wherein the dielectric constant D of the glass circuit board is k Less than about 6.0 when measured at 10 GHz.

[0038] In the thirty-first aspect, the plurality of through holes of the thirtieth aspect may include a first through hole and a second through hole, and the conductive material is disposed on the glass circuit board as a line extending between the first through hole and the second through hole, so that the conductive material forms an electrical path between the first through hole and the second through hole.

[0039] In the thirty-second aspect, the glass circuit board of the thirtieth aspect may include a first major surface and a second major surface opposite to the first major surface, a plurality of through holes including a first through hole extending partially through the thickness of the glass circuit board from the first major surface and a second through hole extending partially through the thickness of the glass circuit board from the second major surface, and a conductive material forms an electrical path between the first through hole and the second through hole.

[0040] In the thirty-third aspect, the conductive material of the thirtieth to thirty-first aspects may be located inside the glass circuit board.

[0041] In a thirty-fourth aspect, the plurality of through-holes of the thirtieth to thirty-first aspects may include a third through-hole, and the electrical path is in electrical communication with the third through-hole.

[0042] In a thirty-fifth aspect, the plurality of through-holes of the thirtieth aspect may include at least one blind through-hole.

[0043] In the thirty-sixth aspect, the loss tangent D of the glass circuit board according to any one of the thirtieth to thirty-fifth aspects is fWhen measured at 30 GHz, it can be less than about 0.001.

[0044] In the thirty-seventh aspect, D of the thirty-sixth aspect f It may be equal to or less than about 0.0005 when measured at 10 GHz.

[0045] In another aspect, a method of manufacturing a glass circuit board is disclosed, comprising forming a plurality of holes in at least one spinodal phase separation glass substrate, the glass substrate comprising a first major surface, a second major surface opposite the first major surface, and a thickness therebetween, the at least one spinodal phase separation glass substrate further comprising a first phase of predominantly SiO2 and a second phase comprising B2O3, and wherein each hole in the plurality of holes extends through the thickness of the spinodal phase separation glass substrate. The method further comprises exposing the at least one spinodal phase separation glass substrate to an acid solution comprising about 5 wt % to about 40 wt % of an acid at a temperature in the range of about 60° C. to about 95° C. for a time in the range of about 8 hours to about 24 hours to remove at least a portion of the second phase from the at least one spinodal phase separation glass substrate, and wherein after the exposure, the total SiO2 content of the spinodal phase separation glass substrate is greater than about 95 mol%, depositing a conductive material in the plurality of holes to form an intermediate circuit board comprising the plurality of holes, and consolidating the intermediate circuit board to form the glass circuit board.

[0046] In aspects, the acid solution can include at least one of HCl, H2SO4, HNO3, HF, or H3PO4. For example, the acid solution can include HCl, such as about 5 wt% HCl.

[0047] In other aspects, the acid solution can include at least one of citric acid or acetic acid.

[0048] In aspects, the at least one spinodal phase separated glass can have an open porosity (excluding porosity originating from pores) greater than about 28% after exposure.

[0049] In aspects, forming the plurality of holes can include laser ablation or chemical etching.

[0050] In some aspects, forming the plurality of holes can include using an RF excited CO 2 laser.

[0051] In other aspects, forming the plurality of holes can include using a laser operating at an ultraviolet wavelength.

[0052] In some implementations, depositing the conductive material may include previously depositing the conductive material as a line between a first through-hole in the plurality of through-holes and a second through-hole in the plurality of through-holes. For example, depositing the conductive material as a line is performed before consolidating the intermediate circuit board.

[0053] In an embodiment, the method may further include heat treating the intermediate circuit board at a temperature in a range of about 500° C. to about 700° C. for a time in a range of about 45 minutes to about 75 minutes.

[0054] In an embodiment, consolidating includes heating the intermediate circuit board to a consolidation temperature in the range of about 850° C. to about 1250° C. for a time in the range of about 1 hour to about 24 hours.

[0055] In aspects, the at least one spinodal phase separation glass substrate may include a plurality of spinodal phase separation glass substrates, the method further comprising forming a plurality of holes in at least a subset of the plurality of spinodal phase separation glass substrates, depositing a conductive material in the plurality of holes of at least the subset of the spinodal phase separation glass substrates to obtain a plurality of intermediate circuit boards, arranging the plurality of intermediate circuit boards to form a stack of intermediate circuit boards, and wherein consolidating comprises consolidating the stack of intermediate circuit boards to form a glass circuit board.

[0056] Prior to consolidation, the stack of intermediate circuit boards may be positioned between a pair of thermally conductive substrates, such as a pair of thermally conductive substrates comprising SiC.

[0057] The method may also include delivering the molten material to a forming body, drawing a glass ribbon from the forming body, and separating a spinodal phase separated glass substrate from the glass ribbon. The molten material may include a 35,000 poise temperature greater than about 1250° C. For example, the glass ribbon may be formed in a fusion downdraw apparatus, wherein the forming body includes a pair of converging forming surfaces joined along a bottom edge of the forming body, where the converging forming surfaces converge.

[0058] Additional features and advantages will be set forth in the following detailed description and, in part, will be apparent to those skilled in the art from this description or may be learned by practicing the embodiments as described herein, including the following detailed description, claims, and accompanying drawings.

[0059] It should be understood that the above summary and the following detailed description are merely exemplary and are intended to provide an overview or framework for understanding the nature and character of the claims. The accompanying drawings are included to provide a further understanding and are incorporated into and constitute a part of this specification. The accompanying drawings illustrate one or more embodiments and together with the description explain the principles and operation of the various embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 is a schematic diagram of an exemplary fusion-drawn glass manufacturing apparatus;

[0061] Figure 2 is a photograph of an exemplary phase-separated glass according to the present disclosure;

[0062] Figure 3 is a graph representing x-ray diffraction (XRD) data, showing no crystallization in the glass, verifying that phase separation occurs between two glass phases;

[0063] Figure 4 It shows two kinds of glass (commercially available non-phase separation glass ( Eagle ) and an exemplary phase-separated glass) as a function of wavelength;

[0064] Figure 5 Corning Eagle XG and Figure 4 A graph of reflectivity as a function of wavelength between exemplary phase-separated glasses.

[0065] Figure 6 For (a) Figure 4 Photographs of (a) a strain range image of an as-drawn sample of an exemplary phase-separated glass and (b) a SEM image of an exemplary phase-separated glass;

[0066] Figure 7 For (a) Figure 4 A photograph of (a) a strain range image of an exemplary phase separation glass sample after heat treatment at 720° C. for 2 hours and (b) a SEM image of an exemplary phase separation glass after heat treatment;

[0067] Figure 8 For (a) Figure 7 (a) a photograph of a strain range image of an exemplary phase separation glass sample after a second heat treatment at 720° C. for 2 hours and (b) a SEM image of the same exemplary phase separation glass sample after the second heat treatment;

[0068] Fig. 9 for Figure 4 SEM image of an exemplary phase-separated glass sample after heat treatment at 745° C. for 24 hours;

[0069] Fig.10 for Figure 4 SEM image of an exemplary phase-separated glass sample after heat treatment at 800° C. for 24 hours;

[0070] Fig.11 for Figure 4 SEM image of an exemplary phase-separated glass sample after heat treatment at 850° C. for 24 hours;

[0071] Fig.12 for Figure 4 SEM image of an exemplary phase-separated glass sample after heat treatment at 900° C. for 24 hours;

[0072] Fig.13is a schematic diagram of the coordinate system used to evaluate the Fourier transform of data for phase-separated glasses;

[0073] Fig.14 is the two-dimensional Fourier transform (2DFT) corresponding to the sample measured from the x-surface;

[0074] Fig.15 are Fourier transform data of three surfaces of an exemplary phase-separated glass sample plotted in an rθ coordinate system, wherein (a) represents an x ​​cross section, (b) represents a y cross section, and (c) represents a z cross section;

[0075] Fig.16 is a schematic diagram of a glass sheet showing points along an edge portion of the glass sheet at which stress measurements are obtained;

[0076] Fig.17 It is shown that during the manufacturing process, when the glass composition is changed from a commercial glass (Corning Eagle XG) to an exemplary phase separation glass, Fig.16 A graph of stress in the corner of a glass plate of , and showing a gradual increase in stress during the transition period;

[0077] Fig.18 is a graph showing the change in loss tangent over time of glasses formed from a commercially available non-phase separation glass composition to an exemplary phase separation glass composition, and showing that the loss tangent gradually decreases;

[0078] Fig.19 is a graph showing stress in a glass sheet made of molten glass when the ratio (B2O3+MgO) / CaO (calculated in wt%) in the molten glass changes with time during a process of changing from a commercially available non-phase-separated glass composition to an exemplary phase-separated glass composition;

[0079] Fig. 20 is a graph of the dielectric constant of an exemplary phase separated glass as MgO is replaced with ZnO;

[0080] Fig.21 yes Fig. 20 A graph of the loss tangent of an exemplary phase separation glass as MgO is replaced with ZnO;

[0081] Fig. 22 is a graph of the dielectric constant of an exemplary phase separation glass as MgO is replaced by ZnO as a function of total RO (or R2O) in an exemplary phase separation glass replacing B2O3 with ZnO;

[0082] Fig.23 yes Fig. 22A graph of the loss tangent of an exemplary phase separation glass of MgO as it is replaced by ZnO as a function of the total RO (or R2O) in the exemplary phase separation glass replacing B2O3 with Zn;

[0083] Fig.24 It is a graph of the resistivity of GS57 and GS17 as the resistivity changes with temperature (°C);

[0084] Fig.25 is a graph of the dielectric constant as a function of mol% La2O3 when La2O3 replaces BaO in glass composition GS72;

[0085] Fig.26 is a graph of the loss tangent as a function of mol% La2O3 when La2O3 replaces Ba in glass composition GS72;

[0086] Fig. 27 is a graph of dielectric constant as a function of mol % La2O3 or Y2O3 when an aluminoborosilicate glass containing Sr-Ba is added on top of an exemplary phase separation glass composition;

[0087] Fig.28 is a graph of loss tangent as a function of mol % La2O3 or Y2O3 when an aluminoborosilicate glass containing Sr-Ba is added on top of an exemplary phase separation glass composition;

[0088] Fig.29 is the D at 10 GHz as a function of the mol% transition metal oxide added as a replacement for CaO in the glass composition k 's picture;

[0089] Fig.30 is the D at 10 GHz as a function of the mol% transition metal oxide added as a replacement for CaO in glass composition GS17 f 's picture;

[0090] Fig.31 D at 10 GHz as a function of the mol % F- added as a replacement for B2O3 in glass composition GS17 k ;

[0091] Fig.32 D at 10 GHz as a function of the mol % F- added as a replacement for B2O3 in glass composition GS17 f ;

[0092] Fig.33 A photograph showing a series of holes formed by UV laser before and after thermal consolidation;

[0093] Fig.34 Show Fig.33 X-ray diffraction pattern on a consolidated substrate (intensity in counts as a function of degrees (2θ));

[0094] Fig.35 is a perspective view of a first intermediate circuit board and a second intermediate circuit board that may be arranged in an intermediate circuit board stack (shown separated for ease of viewing);

[0095] Fig.36 is a cross-sectional edge view of a middle circuit board stack between two thermally conductive substrates;

[0096] Fig.37 Is Fig.35 A top view of a glass circuit board formed by stacking intermediate circuit boards; and

[0097] Fig.38 It is shown along line 38-38 Fig.37 Cross-section of a glass circuit board. DETAILED DESCRIPTION

[0098] In the following detailed description, for the purpose of explanation rather than limitation, exemplary embodiments disclosing specific details are set forth to provide a thorough understanding of the various principles of the present disclosure. However, it will be apparent to those of ordinary skill in the art who benefit from the present disclosure that the present disclosure can be practiced in other embodiments that depart from the specific details disclosed herein. In addition, descriptions of well-known equipment, methods, and materials may be omitted so as not to obscure the description of the various principles of the present disclosure. Finally, wherever applicable, identical reference numerals refer to identical elements.

[0099] Ranges may be expressed herein as from "about" one particular value and / or to "about" another particular value. When such ranges are expressed, another embodiment includes from said one particular value and / or to said another particular value. Similarly, when a value is expressed as an approximation by using the antecedent "about", it is understood that the particular value forms another embodiment. It is also understood that each of the end values ​​in a range is meaningful relative to the other end value and independently of the other end value.

[0100] Unless otherwise specified, all compositions are expressed in terms of mole percent (mol%) of the original batch (i.e., the content of the ingredients). It will be understood by those of ordinary skill in the art that various molten components (e.g., fluorine, alkali metals, boron, etc.) may undergo varying degrees of volatilization (e.g., according to vapor pressure, melting time, and / or melting temperature) during the melting of the components. Therefore, when measuring the final product, the term "about" associated with such components is intended to cover values ​​within about 1 mol% compared to the original batch composition provided herein. In view of the above, it is expected that the composition between the final product and the original batch composition is substantially equivalent.

[0101] Unless otherwise expressly stated, it is not intended that any method described herein be construed as requiring that its steps be performed in a particular order. Therefore, in the absence of a method claim actually reciting an order in which its steps are to be followed or otherwise specifically stating in the claim or description that the steps are to be limited to a particular order, no order is intended to be inferred in any respect. This applies to any possible non-express basis for interpretation, including: matters of logic regarding the arrangement of steps or operational flow; clear meaning derived from grammatical organization or punctuation; and the number or type of embodiments described in this specification.

[0102] A variety of processes may be employed to form the glass articles described herein, including, but not limited to, fusion processes, slot draw processes, and float glass processes.

[0103] As used herein, the singular forms "a", "an", and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to "a component" includes aspects having two or more such components unless the context clearly dictates otherwise.

[0104] Unless otherwise specified, the term "CTE" as used herein refers to the average coefficient of thermal expansion of glass materials, elements, etc. in the present disclosure within a temperature range of 20°C to 300°C.

[0105] The term "dielectric constant (D k )" refers to the dielectric constant of the glass structure, design or article of the present disclosure. Unless otherwise stated, dielectric properties are measured at 10 GHz.

[0106] As used herein, "amorphous" (non-crystalline material) refers to a non-crystalline material that has no long-range atomic order. That is, the material may exhibit short-range atomic order that extends about 1 to 2 atomic spacings longer than a reference atom, but not much beyond this spacing.

[0107] For the sake of brevity, the numerical ranges disclosed herein (including composition ranges or attribute (performance) ranges or a series of ranges) may be appended with the phrase "including all ranges and subranges therebetween", which should be interpreted as including integer or decimal subranges, as if explicitly presented. Thus, for example, a range between 6 and 8 (omitting the unit) implicitly includes a subrange between 6.4 and 8, or a subrange between 6 and 7.2, or a subrange between 6 and 7, etc. In addition, a series of ranges, such as "in the range from 6 to 11 or in the range from 6 to 8" implicitly includes a range from 7 to 10, or a subrange therebetween, such as 7.2 to 10.4, as if explicitly presented, as long as the range does not exceed the minimum or maximum endpoint of the range or series of ranges explicitly presented. Thus, for example, the endpoints of "in the range from 6 to 11 or in the range from 6 to 8" are 6 and 11.

[0108] As used herein, the term "loss tangent" refers to the inherent dissipation of electromagnetic energy (e.g., heat) provided by a particular glass, layer, or laminate structure associated with aspects of the present disclosure. The lower the dielectric losses (e.g., the portion of energy lost as heat), the more effective the dielectric material. Dielectric losses can be parameterized by the loss angle δ or the corresponding loss tangent tan δ. Permittivity is the ability of a material, such as the glass of the present disclosure, to store electrical energy in the presence of an external electric field. Permittivity is a complex quantity because it describes both the phase and amplitude of the polarization associated with an oscillating field. The term "dielectric constant (D k )” and “relative permittivity (ε r )" are used interchangeably in this disclosure and are defined as the ratio between the real part of the complex permittivity (absolute permittivity, ε) and the permittivity of free space (vacuum permittivity, ε0). r >1 is considered a dielectric material and a poor conductor of electricity. Materials with low dielectric constants can withstand stronger electrostatic fields without dielectric breakdown. Dielectric breakdown causes the material to conduct electrical current, which for most solid materials results in material damage. "Loss tangent" is expressed as the ratio of the imaginary part to the real part of the complex permittivity. In general, the dielectric constant and loss tangent of a material depend on the frequency of the external field. Therefore, dielectric properties measured in the kHz range may not be representative of the dielectric properties at microwave frequencies. In addition, unless otherwise stated, the "loss tangent" and "dielectric constant (D)" of the glasses disclosed herein are not intended to be construed as "loss tangent" or "dielectric constant (D)". k )" properties can be measured at frequencies of 1 GHz or higher based on a separated pillar dielectric resonator (SPDR) or open cavity resonator configuration, in accordance with techniques understood by those of ordinary skill in the art of this disclosure. The particular method can be selected based on the sample thickness and its lateral dimensions.

[0109] As used herein, molten glass refers to a molten material formed by heating batch materials in a melting vessel, the molten glass having a viscosity ranging from about 1 kilopoise (kP or kPoise) to about 200 kPoise.

[0110] As used herein, spinodal decomposition refers to a phase transition in which a material (e.g., a glass material) having a single thermodynamic phase separates into multiple coexisting but independent phases (e.g., two phases) without nucleation (e.g., spontaneous separation). The various phases may be dispersed throughout the glass and interconnected. The various phases may exist in approximately equal proportions and occupy approximately equal volumes. Therefore, the term "phase separation glass" used herein refers to a glass having at least two stable interconnected phases produced by spinodal decomposition, wherein the interconnected second phase is dispersed throughout the interconnected first phase. One phase (e.g., the first or primary phase) may be rich in a first chemical substance (e.g., SiO2), while the second (e.g., secondary) phase may be rich in a second chemical substance (e.g., B2O3). That is, the first phase may, for example, mainly include all SiO2, while the second phase mainly includes all B2O3. That is, for example, the first phase may include a majority of SiO2, while the second phase may include a majority of B2O3. The term "majority" herein refers to greater than 50 mol%.

[0111] Consolidation as used herein (e.g., consolidation), also referred to as firing, refers to a process in which a porous material is subjected to heating conditions suitable for causing the material to reach at least a softening temperature, e.g., a melting temperature, wherein the pores of the porous material close and the material is no longer porous and becomes a solid article, e.g., a solid glass article without pores distributed therein.

[0112] The glass and glass articles of the present disclosure may be suitable for use in electronic devices, electronic device substrates, and other similar applications that enable higher frequency communications in devices without significantly reducing performance associated with other non-electrical device requirements. For example, because higher frequency communication signals are used in these devices, the signals must pass through various physical barriers that would otherwise attenuate or block the signals. Therefore, the glass and / or glass articles of the present disclosure may be very suitable for use as these physical barriers. Examples of these physical barriers include electrically insulating substrates used to manufacture electronic circuits and signal transmission structures, electronic device covers, and other related structures that can be used to accommodate electronic circuits and other electronic device components used in electronic devices that operate at high signal frequencies.

[0113] In some embodiments, the glasses of the present disclosure may be suitable for use as substrates in PCBs. PCBs typically include an insulating layer laminated with a conductive film. In some embodiments, the glasses of the present disclosure may be characterized by low loss tangent and mechanical properties, suitable for use as insulating layers in PCBs, optionally in combination with one or more polymer substrate layers. Optionally, the glasses of the present disclosure may be substantially free of alkali metals to reduce the likelihood of ion migration into electronic components (e.g., thin film transistors) during circuit board processing.

[0114] Some aspects of the present disclosure also relate to glass having properties suitable for manufacturing, such as slot draw processes and overflow fusion draw processes. The fusion draw process is an industrial technology that has been used to manufacture thin glass sheets on a large scale, such as glass sheets having a thickness of less than about 3 mm, such as less than about 1 mm, less than about 0.7 mm, or even less than about 0.1 mm. The fusion draw process can produce thin glass sheets with high flatness and surface quality compared to other flat glass manufacturing technologies, such as float or slot draw processes. Therefore, the fusion draw process is often an ideal manufacturing technology for manufacturing thin glass substrates, such as cover glass for liquid crystal displays and various personal electronic devices.

[0115] Figure 1 An exemplary molten glass manufacturing preparation 10 is shown. The glass manufacturing apparatus 10 includes a glass melting furnace 12, which includes a melting vessel 14. In addition to the melting vessel 14, the glass melting furnace 12 may optionally include one or more additional components, such as heating elements (e.g., burners and / or electrodes) configured to heat raw materials and convert the raw materials into molten material (hereinafter referred to as molten glass). For example, the melting vessel 14 may be an electrically enhanced melting vessel, where energy is added to the raw materials by burners and direct heating, where an electric current is passed through the raw materials so that the electric current adds energy by Joule heating the raw materials.

[0116] Glass melting furnace 12 may include other thermal management devices (e.g., insulation components) to reduce heat loss from the melting vessel. Glass melting furnace 12 may include electronic and / or electromechanical devices that assist in melting raw materials into a glass melt. Glass melting furnace 12 may include support structures (e.g., support chassis, support members, etc.) or other components.

[0117] The melting vessel 14 can be formed of a refractory material, such as a refractory ceramic material including alumina or zirconia, although the refractory ceramic material can include other refractory materials, such as yttrium (e.g., yttria, yttria-stabilized zirconia, yttrium phosphate), zircon (ZrSiO4) or alumina-zirconia-silica or even chromium oxide, which can be used interchangeably or in any combination. In some examples, the melting vessel 14 can be composed of refractory ceramic bricks.

[0118] The glass melting furnace 12 can be incorporated as a component of a glass manufacturing apparatus that is configured to manufacture glass products, such as glass ribbons, although the glass manufacturing apparatus can be configured to form other glass products without limitation, such as glass rods, glass tubes, glass envelopes (e.g., glass envelopes for lighting devices such as light bulbs), and glass lenses. In some examples, the glass melting furnace 12 can be included in a glass manufacturing apparatus that includes a slot draw apparatus, a float tank apparatus, a down draw apparatus (e.g., a fusion down draw apparatus), an up draw apparatus, a press apparatus, a rolling apparatus, a tube draw apparatus, or any other glass manufacturing apparatus that can benefit from the present disclosure. For example, Figure 1 A glass melting furnace 12 is schematically shown as part of the fusion down-draw glass manufacturing apparatus 10 for fusion drawing a glass ribbon for subsequent processing into individual glass sheets or winding the glass ribbon onto a reel. As used herein, fusion drawing involves flowing molten glass over the inclined (e.g., converging) side surfaces of a forming body, wherein the resulting streams of molten material meet or "fuse" at the bottom of the forming body to form a glass ribbon.

[0119] The glassmaking facility 10 may optionally include upstream glassmaking equipment 16 located upstream of the melting vessel 14. In some examples, a portion or all of the upstream glassmaking equipment 16 may be incorporated as part of the glass melting furnace 12.

[0120] like Figure 1 As shown, the upstream glass manufacturing equipment 16 may include a raw material storage bin 18, a raw material delivery device 20, and a motor 22 connected to the raw material delivery device 20. The raw material storage bin 18 may be configured to store raw materials 24, which may be fed into the melting vessel 14 of the glass melting furnace 12 through one or more feed ports, as shown by arrows 26. The raw materials 24 generally include one or more glass-forming metal oxides and one or more modifiers. In some examples, the raw material delivery device 20 may be powered by the motor 22 to deliver a predetermined amount of raw materials 24 from the raw material storage bin 18 to the melting vessel 14. In a further example, the motor 22 may power the raw material delivery device 20, thereby introducing the raw material 24 at a controlled rate based on the liquid level of the molten glass sensed downstream of the melting vessel 14 relative to the flow direction of the molten glass. The raw materials 24 in the melting vessel 14 may then be heated to form a molten glass 28. Typically, the raw materials are added to the melting vessel in the form of particles such as various "sands". The raw material 24 may also include waste glass (i.e., cullet) from previous melting and / or forming operations. A burner may be used to initiate the melting process. In an electrically enhanced melting process, once the burner has sufficiently reduced the electrical resistance of the raw material, electrical enhancement may be initiated by creating an electrical potential between electrodes in contact with the raw material, thereby establishing an electrical current through the raw material, which typically enters or is in a molten state.

[0121] The glass manufacturing apparatus 10 may also include a downstream glass manufacturing apparatus 30 located downstream of the glass melting furnace 12 relative to the flow direction of the molten glass 28. In some examples, a portion of the downstream glass manufacturing apparatus 30 may be incorporated as a portion of the glass melting furnace 12. For example, the first connecting pipe 32 discussed below or other portions of the downstream glass manufacturing apparatus 30 may be incorporated as a portion of the glass melting furnace 12.

[0122] The downstream glass manufacturing equipment 30 may include a first conditioning chamber, such as a clarification vessel 34, which is located downstream of the melting vessel 14 and is connected to the melting vessel 14 by the first connecting pipe 32 mentioned above. In some examples, the molten glass 28 can be gravity fed from the melting vessel 14 to the clarification vessel 34 through the first connecting pipe 32. Therefore, the first connecting pipe 32 provides a flow path from the melting vessel 14 to the clarification vessel 34 for the molten glass 28. However, other conditioning chambers may be located downstream of the melting vessel 14, such as between the melting vessel 14 and the clarification vessel 34. In some embodiments, a conditioning chamber may be used between the melting vessel and the clarification chamber. For example, the molten glass from the main melting vessel can be further heated in a secondary melting (conditioning) vessel, or cooled in a secondary melting vessel to a temperature lower than the temperature of the molten glass in the main melting vessel before entering the clarification chamber.

[0123] Bubbles can be removed from the molten glass 28 by various techniques. For example, the raw material 24 may include a polyvalent compound (i.e., a clarifier), such as tin oxide, which, when heated, undergoes a chemical reduction reaction and releases oxygen. Other suitable clarifiers may include (but are not limited to) arsenic, antimony, iron and / or cerium, but due to the toxicity of arsenic and antimony, their use may be discouraged in some applications for environmental reasons. The clarification vessel 34 is heated, for example, to a temperature higher than the temperature inside the melting vessel, thereby heating the clarifier to a reaction temperature sufficient for chemical reduction. One or more clarifiers included in the molten glass undergo chemical reduction under temperature induction, and the oxygen generated diffuses into the bubbles generated during the melting process. Then, the bubbles that expand as the buoyancy increases rise to the free surface of the molten glass in the clarification vessel, and then are discharged from the clarification vessel, for example, through an exhaust pipe that is connected to the atmospheric fluid above the free surface.

[0124] The downstream glass manufacturing equipment 30 may also include another conditioning chamber, such as a mixing device 36, such as a stirring container, for mixing the molten glass flowing out from the downstream of the clarification container 34. The mixing device 36 can be used to provide a uniform glass melt composition, thereby reducing the chemical and / or thermal inhomogeneities that may exist in the molten glass leaving the clarification container. As shown, the clarification container 34 can be connected to the mixing device 36 by a second connecting pipe 38. Therefore, the molten glass 28 can be gravity-fed from the clarification container 34 to the mixing device 36 by the second connecting pipe 38. Typically, the molten glass in the mixing device 36 includes a free surface, wherein the free (e.g., gaseous) volume extends between the free surface and the top of the mixing device. Although the mixing device 36 shown is located downstream of the clarification container 34 relative to the flow direction of the molten glass 28, in other embodiments, the mixing device 36 may be located upstream of the clarification container 34. The downstream glass manufacturing equipment 30 may include a plurality of mixing devices, such as a mixing device upstream of the clarification container 34 and a mixing device downstream of the clarification container 34. When used, a plurality of mixing devices may have the same design, or they may have designs that are different from each other. One or more of the vessels and / or conduits disclosed herein may include static mixing blades positioned therein to further facilitate mixing and subsequent homogenization of the molten material.

[0125] The downstream glass manufacturing apparatus 30 may also include another conditioning chamber, such as a delivery vessel 40, located downstream of the mixing apparatus 36. The delivery vessel 40 may act as an accumulator and / or flow controller to provide a consistent flow of molten glass 28 to the forming body 42 through an outlet conduit 44. In some embodiments, the molten glass in the delivery vessel 40 may include a free surface, wherein the free volume extends upward from the free surface to the top of the delivery vessel. As shown, the mixing scheme 36 may be connected to the delivery vessel 40 via a third connecting conduit 46, wherein the molten glass 28 may be gravity fed from the mixing scheme 36 to the delivery vessel 40 via the third connecting conduit 46.

[0126] The downstream glass manufacturing apparatus 30 may also include a forming apparatus 48 configured to form a glass product, such as a glass ribbon. Thus, the forming apparatus 48 may include a down-draw apparatus, such as an overflow down-draw apparatus, in which the outlet conduit 44 is positioned to deliver the molten glass 28 from the delivery container 40 to the inlet conduit 50 of the forming body 42. The forming body in the fusion down-draw glass manufacturing apparatus may include a trough 52 located on the upper surface of the forming body and opposite converging forming surfaces 54 converging in a drawing direction 56 along the bottom edge (root) 58 of the forming body. The molten glass delivered to the forming body trough 52 via the delivery container 40, the outlet conduit 44, and the inlet conduit 50 overflows the wall of the trough 52 and descends along the converging forming surfaces 54 as separate molten glass streams. The separate molten glass streams merge below and along the root 58 to produce a molten glass ribbon, which is pulled out from the root 58 along the drawing direction 56 by applying downward tension to the molten glass ribbon (e.g., by gravity and opposite counter-rotating pulling rollers 62). As the molten glass cools and the viscosity of the molten glass increases, the applied downward tension and the temperature of the molten glass can be used to control the size of the glass ribbon. Thus, the molten glass ribbon undergoes a viscosity transition from a viscous state to a viscoelastic state to an elastic state and acquires mechanical properties that provide the glass ribbon 60 with stable dimensional characteristics. The glass ribbon 60 can then be scored and then divided into shorter lengths, such as into glass sheets 64, using a scoring device 66.

[0127] Components of the downstream glass manufacturing equipment 30 (including any one or more of the connecting pipes 32, 38, 46, the clarification vessel 34, the mixing device 36, the transport vessel 40, the outlet pipe 44 or the inlet pipe 50) can be formed of a precious metal. Suitable precious metals include platinum group metals selected from the group consisting of platinum, iridium, rhodium, osmium, ruthenium and palladium, or alloys thereof. For example, the downstream components of the glass manufacturing equipment can be formed of a platinum-rhodium alloy, the alloy comprising about 70% by weight to about 90% by weight of platinum and about 10% by weight to about 30% by weight of rhodium.

[0128] In order to facilitate the fusion drawing process, the glass preferably has a sufficiently high liquidus viscosity (i.e., the viscosity of the molten glass at the liquidus temperature). A higher liquidus viscosity can facilitate the forming of the glass by a down-drawing process (e.g., fusion forming). The liquidus viscosity of the molten formable glass may be greater than about 140 kPoise. In addition, the fusion drawing process can be carried out within a certain viscosity range. The glass is generally delivered to the trough of the forming body with a viscosity corresponding to about 20,000-35,000 poise, and leaves the root of the forming body in a viscous ribbon corresponding to a viscosity of about 100,000 poise or higher. A temperature corresponding to a viscosity of 35,000 poise is generally used as a guide for the temperature at which the glass is delivered to the forming body trough for fusion drawing. The glass of the present disclosure may have a temperature corresponding to a 35,000 poise temperature (referred to herein as "35,000 poise temperature"), which is conducive to forming by a down-drawing process, such as a 35,000 poise temperature greater than about 1250°C. Typically, it is desirable to maintain a lower temperature of 35,000 poise to minimize undesirable creep of the forming body refractory material over time.

[0129] The temperature corresponding to a viscosity of 200 poise is often used as a guide to suitable melting temperatures for a glass. In some embodiments, the glass of the present disclosure may be characterized by a high 200 poise temperature (also referred to as a poise melting point) (referred to herein as a "200 poise melting point") to facilitate forming. Preferably, the difference between the 200 poise temperature and the 35,000 poise temperature is less than or equal to about 450°C, for example, equal to or less than about 420°C, such as equal to or less than about 400°C.

[0130] In some glass compositions described herein, SiO2 can be used as a primary glass former. The phase separation glass disclosed herein can include a total amount of SiO2 in the range of about 57 mol% to about 71 mol%, such as in the range of about 57 mol% to about 70 mol%, in the range of about 57 mol% to about 69 mol%, in the range of about 57 mol% to about 68 mol%, in the range of about 57 mol% to about 67 mol%, in the range of about 57 mol% to about 66 mol%, in the range of about 57 mol% to about 65 mol%, in the range of about 57 mol% to about 64 mol%, in the range of about 57 mol% to about 63 mol%, in the range of about 57 mol% to about 62 mol%, in the range of about 57 mol% to about 61 mol%, in the range of about 57 mol% to about 60 mol%, or in the range of about 57 mol% to about 59 mol%, or in the range of about 57 mol% to about 58 mol%, including all ranges and sub-ranges therebetween. In an embodiment, the glass composition may include SiO2 in a range of about 58 mol% to about 71 mol%, in a range of about 59 mol% to about 71 mol%, in a range of about 60 mol% to about 71 mol%, in a range of about 61 mol% to about 71 mol%, in a range of about 62 mol% to about 71 mol%, in a range of about 63 mol% to about 71 mol%, in a range of about 64 mol% to about 71 mol%, in a range of about 65 mol% to about 71 mol%, in a range of about 66 mol% to about 71 mol%, in a range of about 67 mol% to about 71 mol%, in a range of about 68 mol% to about 71 mol%, in a range of about 69 mol% to about 71 mol%, or in a range of about 70 mol% to about 71 mol%, including all ranges and sub-ranges therebetween.

[0131] In some embodiments, the glass of the present disclosure may include a total amount of SiO2 in an amount within a range of about 67.2 mol% to about 69 mol%, within a range of about 67.4 mol% to about 69 mol%, within a range of about 67.6 mol% to about 69 mol%, within a range of about 67.8 mol% to about 69 mol%, within a range of about 68.0 mol% to about 69 mol%, within a range of about 68.2 mol% to about 69 mol%, within a range of about 68.4 mol% to about 69 mol%, within a range of about 68.6 mol% to about 69 mol%, within a range of about 68.8 mol% to about 69 mol%, and all ranges and sub-ranges therebetween. In an embodiment, the glass may include SiO in a range of about 67mol% to about 68.6mol%, in a range of about 67mol% to about 68.4mol%, in a range of about 67mol% to about 68.2mol%, in a range of about 67mol% to about 68.0mol%, in a range of about 67mol% to about 67.8mol%, in a range of about 67mol% to about 67.6mol%, in a range of about 67mol% to about 67.4mol%, including all ranges and sub-ranges therebetween. As used herein, the term "total amount" in the context of phase-separated glass refers to the amount of chemical substances in the phase-separated glass, without regard to the position of the chemical substances in any single phase present in the glass. Thus, for example, the total amount of SiO in a phase-separated glass comprising two phases refers to the combined amount of SiO that may be present in the two phases.

[0132] The phase-separated glass of the present disclosure may contain a total amount of Al2O3 in the range of about 3 mol% to about 13 mol%, for example, in the range of about 3 mol% to about 12 mol%, in the range of about 3 mol% to about 11 mol%, in the range of about 3 mol% to about 10 mol%, in the range of about 3 mol% to about 9 mol%, in the range of about 3 mol% to about 8 mol%, in the range of about 3 mol% to about 7 mol%, in the range of about 3 mol% to about 6 mol%, in the range of about 3 mol% to about 5 mol%, or in the range of about 3 mol% to about 4 mol%, including all ranges and sub-ranges therebetween. In an embodiment, the glass may include Al2O3 in a range of about 4 mol% to about 13 mol%, in a range of about 5 mol% to about 13 mol%, in a range of about 6 mol% to about 13 mol%, in a range of about 7 mol% to about 13 mol%, in a range of about 8 mol% to about 13 mol%, in a range of about 9 mol% to about 13 mol%, in a range of about 10 mol% to about 13 mol%, in a range of about 11 mol% to about 13 mole%, or in a range of about 12 mol% to about 13 mol%, including all ranges and sub-ranges therebetween. In some embodiments, the glass of the present disclosure may include Al2O3 in a range of about 7.6 mol% to about 8.7 mol%, for example, in a range of about 7.6 mol% to about 8.6 mol%, in a range of about 7.6 mol% to about 8.5 mol%, in a range of about 7.6 mol% to about 8.4 mol%, in a range of about 7.6 mol% to about 8.3 mol%, in a range of about 7.6 mol% to about 8.2 mol%, in a range of about 7.6 mol% to about 8.1 mol%, in a range of about 7.6 mol% to about 8.0 mol%, in a range of about 7.6 mol% to about 7.9 mol%, in a range of about 7.6 mol% to about 7.8 mol%, or in a range of about 7.6 mol% to about 7.7 mol%, including all ranges and sub-ranges therebetween. In an embodiment, the glass may include Al2O3 in a range of about 7.7 mol% to about 8.7 mol%, in a range of about 7.8 mol% to about 8.7 mol%, in a range of about 7.9 mol% to about 8.7 mol%, in a range of about 8.0 mol% to about 8.7 mol%, in a range of about 8.1 mol% to about 8.7 mol%, in a range of about 8.2 mol% to about 8.7 mol%, in a range of about 8.3 mol% to about 8.7 mol%, in a range of about 8.4 mol% to about 8.7 mol%, in a range of about 8.5 mol% to about 8.7 mol%, or in a range of about 8.6 mol% to about 8.7 mol%, including all ranges and sub-ranges therebetween.

[0133] The phase-separated glass of the present disclosure may contain a total amount of B2O3 in the range of about 9% to about 20%, for example, in the range of about 10 mol% to about 20 mol%, in the range of about 11 mol% to about 20 mole%, in the range of about 12 mol% to about 20 mol%, in the range of about 13 mol% to about 20 mol%, in the range of about 14 mol% to about 20 mol%, in the range of about 15 mol% to about 20 mol%, in the range of about 16 mol% to about 20 mole%, in the range of about 17 mol% to about 20 mol%, in the range of about 18 mol% to about 20 mol%, or in the range of about 19 mol% to about 20 mol%, including all ranges and sub-ranges therebetween. In an embodiment, the glass may include B2O3 in a range of about 9% to about 18%, for example, in a range of about 9 mol% to about 18 mol%, in a range of about 9 mol% to about 17 mole%, in a range of about 9 mol% to about 16 mol%, in a range of about 9 mol% to about 15 mol%, in a range of about 9 mol% to about 14 mol%, in a range of about 9 mol% to about 13 mol%, in a range of about 9 mol% to about 12 mole%, in a range of about 9 mol% to about 11 mol%, or in a range of about 9 mol% to about 10 mol%, including all ranges and sub-ranges therebetween. In some embodiments, the glass of the present disclosure may include B2O3 in a range of about 11.9 mol% to about 14.1 mol%, for example, in a range of about 11.9 mol% to about 13.8 mol%, in a range of about 11.9 mol% to about 13.6 mol%, in a range of about 11.9 mol% to about 13.4 mol%, in a range of about 11.9 mol% to about 13.2 mol%, in a range of about 11.9 mol% to about 13.0 mol%, in a range of about 11.9 mol% to about 12.8 mol%, in a range of about 11.9 mol% to about 12.6 mol%, in a range of about 11.9 mol% to about 12.4 mol%, or in a range of about 11.9 mol% to about 12.2 mol%, including all ranges and sub-ranges therebetween.In an embodiment, the glass may include Al2O3 in a range of about 12.0 mol% to about 14.1 mol%, in a range of about 12.2 mol% to about 14.1 mol%, in a range of about 12.3 mol% to about 14.1 mol%, in a range of about 12.4 mol% to about 14.1 mol%, in a range of about 12.5 mol% to about 14.1 mol%, in a range of about 12.6 mol% to about 14.1 mol%, in a range of about 12.8 mol% to about 14.1 mol%, in a range of about 13.0 mol% to about 14.1 mol%, in a range of about 13.2 mol% to about 14.1 mol%, in a range of about 13.4 mol% to about 14.1 mol%, in a range of about 13.6 mol% to about 14.1 mol%, or in a range of about 13.8 mol% to about 14.1 mol%, including all ranges and sub-ranges therebetween.

[0134] Increasing the amount of SiO2 can reduce the dielectric constant and loss tangent of the glass at frequencies of 10 GHz or higher; however, increasing the amount of SiO2 may reduce the formability of the glass, particularly the formability of the down-draw process. For example, as the amount of SiO2 increases, the liquidus temperature of the glass may increase. Pure SiO2 has a lower CTE and is incompatible with the down-draw process due to its high melting temperature. B2O3 can be added to reduce the viscosity of the glass and reduce the liquidus temperature to facilitate glass forming, particularly through the down-draw process. B2O3 can act to reduce the liquidus temperature faster than the viscosity, and thus can improve the liquidus viscosity for the down-draw process. Al2O3 can reduce the liquidus temperature and thereby increase the liquidus viscosity. Therefore, the amount of SiO2, B2O3, and optionally Al2O3 can be selected according to the present disclosure to balance the desired dielectric properties and formability of the glass.

[0135] In some aspects of the present disclosure, the total amount of SiO2, B2O3, and Al2O3 in the glass can be selected so that the ratio of B2O3: (Al2O3 + SiO2) is about 0.1 to about 0.3, such as in the range of about 0.12 to about 0.3, in the range of about 0.14 to about 0.3, in the range of about 0.16 to about 0.3, in the range of about 0.18 to about 0.3, in the range of about 0.2 to about 0.3, in the range of about 0.22 to about 0.3, in the range of about 0.24 to about 0.3, in the range of about 0.26 to about 0.3, or in the range of about 0.28 to about 0.3, including all ranges and sub-ranges therebetween. In some aspects, the ratio of B2O3: (Al2O3 + SiO2) can be in the range of about 0.16 to about 0.18, about 0.16 to about 0.17, or about 0.17 to about 0.18, including all ranges and sub-ranges therebetween.

[0136] In some aspects, the total amount of SiO2 and B2O3 can be selected so that the sum of SiO2 plus B2O3 is in the range of about 77 mol% to about 84 mol%, such as in the range of about 78 mol% to about 84 mol%, in the range of about 79 mol% to about 84 mol%, in the range of about 80 mol% to about 84 mol%, in the range of about 81 mol% to about 84 mol%, in the range of about 82 to about 84 mol%, or in the range of about 83 mol% to about 84 mol%. In aspects, the glass can include so that the sum of SiO2 plus B2O3 is in the range of about 77 mol% to about 83 mol%, in the range of about 77 mol% to about 82 mol%, in the range of about 77 mol% to about 81 mol%, in the range of about 77 mol% to about 80 mol%, in the range of about 77 mol% to about 79 mol%, or in the range of about 77 mol% to about 78 mol%, including all ranges and sub-ranges therebetween.

[0137] In some aspects, the total amount of SiO2, B2O3, and Al2O3 in the phase-separated glass can be selected so that the sum of SiO2 plus B2O3 plus Al2O3 is in the range of about 85 mol% to about 93 mol%, for example, in the range of about 86 mol% to about 93 mol%, in the range of about 87 mol% to about 93 mol%, in the range of about 88 mol% to about 93 mol%, in the range of about 89 mol% to about 93 mol%, in the range of about 90 mol% to about 93 mol%, in the range of about 91 mol% to about 93 mol%, or in the range of about 92 mol% to about 93 mol%, including all ranges and sub-ranges therebetween. In aspects, the glass may include the sum of SiO2, B2O3, and Al2O3 in a range of about 85 mol% to about 92 mol%, in a range of about 85 mol% to about 91 mol%, in a range of about 85 mol% to about 90 mol%, in a range of about 85 mol% to about 89 mol%, in a range of about 85 mol% to about 88 mol%, in a range of about 85 mol% to about 87 mol%, or in a range of about 85 mol% to about 86 mol%, including all ranges and sub-ranges therebetween.

[0138] According to some aspects, when present, the phase separated glass can include one or more alkaline earth oxides (RO), wherein the RO comprises MgO, CaO, BaO, and / or SrO.

[0139] MgO can facilitate glass melting by lowering the melting temperature, and can facilitate glass formation by lowering the liquidus temperature and increasing the liquidus viscosity, while also maintaining a high annealing point. The phase-separated glass of the present disclosure may contain a total amount of MgO in the range of about 4% to about 6%, such as in the range of about 4 mol% to about 5.8 mol%, in the range of about 4 mol% to about 5.6 mole%, in the range of about 4 mol% to about 5.4 mol%, in the range of about 4 mol% to about 5.2 mol%, in the range of about 4 mol% to about 5 mol%, in the range of about 4 mol% to about 4.8 mol%, in the range of about 4 mol% to about 4.6 mole%, in the range of about 4 mol% to about 4.4 mol%, or in the range of about 4 mol% to about 4.2 mol%, including all ranges and sub-ranges therebetween. In aspects, the glass can include MgO in a range of about 4.2 mol % to about 6 mol %, in a range of about 4.4 mol % to about 6 mol %, in a range of about 4.6 mol % to about 6 mol %, in a range of about 4.8 mol % to about 6 mole %, in a range of about 5 mol % to about 6 mol %, in a range of about 5.2 mol % to about 6 mol %, in a range of about 5.4 mol % to about 6 mol %, in a range of about 5.6 mol % to about 6 mol %, or in a range of about 5.8 mol % to about 6 mole %, including all ranges and subranges therebetween.

[0140] The phase-separated glass of the present disclosure may include a total amount of CaO in the range of about 3 mol% to about 6 mol%, for example, in the range of about 3.2 mol% to about 6 mol%, in the range of about 3.4 mol% to about 6 mole%, in the range of about 3.6 mol% to about 6 mol%, in the range of about 3.8 mol% to about 6 mol%, in the range of about 4 mol% to about 6 mol%, in the range of about 4.2 mol% to about 6 mol%, in the range of about 4.4 mol% to about 6 mole%, in the range of about 4.6 mol% to about 6 mol%, in the range of about 4.8 mol% to about 6 mol%, in the range of about 5 mol% to about 6 mol%, in the range of about 5.2 mol% to about 6%, in the range of about 5.4 mol% to about 6 mol%, in the range of about 5.6 mol% to about 6 mole%, or in the range of about 5.8 mol% to about 6 mol%, including all ranges and sub-ranges therebetween. In an embodiment, the glass may include CaO in a range of about 3 mol% to about 5.8 mol%, in a range of about 3 mol% to about 5.6 mol%, in a range of about 3 mol% to about 5.4 mol%, in a range of about 3 mol% to about 5.2 mol%, in a range of about 3 mol% to about 5 mol%, in a range of about 3 mol% to about 4.8 mol%, in a range of about 3 mol% to about 4.6 mol%, in a range of about 3 mol% to about 4.4 mol%, in a range of about 3 mol% to about 4.2 mol%, in a range of about 3 mol% to about 4 mol%, in a range of about 3 mol% to about 3.8 mol%, in a range of about 3 mol% to about 3.6 mol%, in a range of about 3 mol% to about 3.4 mol%, or in a range of about 3 mol% to about 3.2 mole%, including all ranges and sub-ranges therebetween.

[0141] The phase-separated glass of the present disclosure may include a total amount of SrO of less than about 0.2 mol%, for example, within a range of about 0% to about 0.2 mol%, for example, within a range of about 0.02 mol% to about 0.2 mol%, within a range of about 0.04 mol% to about 0.2 mol%, within a range of about 0.06 mol% to about 0.2 mol%, within a range of about 0.08 mol% to about 0.2 mol%, within a range of about 0.1 mol% to about 0.2 mol%, within a range of about 0.12 mol% to about 0.2 mol%, within a range of about 0.14 mol% to about 0.2 mol%, within a range of about 0.16 mol% to about 0.2 mol%, or within a range of about 0.18 mol% to about 0.2 mol%, including all ranges and sub-ranges therebetween. In an embodiment, the glass may include SrO in a range of about 0 mol% to about 0.18 mol%, in a range of about 0 mol% to about 0.16 mol%, in a range of about 0 mol% to about 0.14 mol%, in a range of about 0 mol% to about 0.12 mol%, in a range of about 0 mol% to about 0.1 mol%, in a range of about 0 mol% to about 0.08 mol%, in a range of about 0 mol% to about 0.06 mol%, in a range of about 0 mol% to about 0.4 mol%, or in a range of about 0 mol% to about 0.02 mol%, including all ranges and sub-ranges therebetween.

[0142] The phase-separated glass of the present disclosure may optionally contain a total amount of BaO of less than about 1 mol%, for example, within a range of about 0% to about 1 mol%, such as within a range of about 0.1 mol% to about 1 mol%, within a range of about 0.2 mol% to about 1 mol%, within a range of about 0.3 mol% to about 1 mol%, within a range of about 0.4 mol% to about 1 mol%, within a range of about 0.5 mol% to about 1 mol%, within a range of about 0.6 mol% to about 1 mol%, within a range of about 0.7 mol% to about 1 mol%, within a range of about 0.8 mol% to about 1 mol%, or within a range of about 0.9 mol% to about 1 mol%, including all ranges and sub-ranges therebetween. In aspects, the glass can include BaO in a range of about 0 mol% to about 0.9 mol%, in a range of about 0 mol% to about 0.8 mol%, in a range of about 0 mol% to about 0.7 mol%, in a range of about 0 mol% to about 0.6 mol%, in a range of about 0 mol% to about 0.5 mol%, in a range of about 0 mol% to about 0.4 mol%, in a range of about 0 mol% to about 0.3 mol%, in a range of about 0 mol% to about 0.2 mol%, or in a range of about 0 mol% to about 0.1 mol%, including all ranges and sub-ranges therebetween.

[0143] In some aspects, one or more alkaline earth oxides MgO, CaO, BaO, SrO can be present in a combined amount from about 4.6 mol% to about 14.2 mol%, for example, in a range of about 4.8 mol% to about 14.2 mol%, in a range of about 5 mol% to about 14.2 mol%, in a range of about 5.4 mol% to about 14.2 mol%, in a range of about 5.8 mol% to about 14.2 mol%, in a range of about 6.2 mol% to about 14.2 mol%, in a range of about 7.2 mol% to about 14.2 mol%, in a range of about 8.2 mol% to about 14.2 mol%, in a range of about 9.2 mol% to about 14.2 mol%, in a range of about 10.2 mol% to about 14.2 mol%, in a range of about 11.2 mol% to about 14.2 mol%, in a range of about 12.2 mol% to about 14.2 mol%, or in a range of about 13.2 mol% to about 14.2 mol%, including all ranges and sub-ranges therebetween. In aspects, the one or more alkaline earth oxides can be present in a combined amount within a range of about 4.6 mol% to about 13.6 mol%, within a range of about 4.6 mol% to about 12.6 mol%, within a range of about 4.6 mol% to about 11.6 mol%, within a range of about 4.6 mol% to about 10.6 mol%, within a range of about 4.6 mol% to about 9.6 mol%, within a range of about 4.6 mol% to about 8.6 mol%, within a range of about 4.6 mol% to about 7.6 mol%, within a range of about 4.6 mol% to about 6.6 mol%, or within a range of about 4.6 mol% to about 5.6 mol%, including all ranges and sub-ranges therebetween.

[0144] According to some aspects of the present disclosure, a phase separated glass may include MgO and at least one additional alkaline earth oxide (RO) selected from CaO, BaO, and SrO. In some examples, the combination of MgO and at least one additional RO may produce a glass having a lower dielectric constant and / or loss tangent than a glass including MgO or another RO alone.

[0145] In some aspects, as described above and consistent with the total amount of Al2O3 present in the glass, the total amount of MgO and the total amount of additional RO are selected such that RO 总 With Al2O3(RO 总 :Al2O3) ratio is greater than 1. Providing a 总 Glass with :Al2O3>1 can facilitate the formation of manufacturable glass that can be drawn using conventional glass forming processes, such as a fusion process.

[0146] In some aspects, MgO and RO 总 (MgO:RO总 ) can be in the range of about 0.3 to about 4.7, such as in the range of about 0.3 to about 4.5, in the range of about 0.3 to about 0.4, in the range of about 0.3 to about 3.5, in the range of about 0.3 to about 3, in the range of about 0.3 to about 2.5, or in the range of about 0.3 to about 2, including all ranges and sub-ranges therebetween. In embodiments, MgO and RO 总 The overall ratio may be in the range of about 0.5 to about 4.7, in the range of about 0.75 to about 4.7, in the range of about 1 to about 4.7, in the range of about 1.5 to about 4.7, in the range of about 2 to about 4.7, in the range of about 2.5 to about 4.7, in the range of about 3 to about 4.7, in the range of about 3.5 to about 4.7, or in the range of about 4 to about 4.7, including all ranges and sub-ranges therebetween.

[0147] For a given phase separated glass, by reducing the concentration of a single RO species present in the glass, a lower dielectric constant and / or loss tangent can be achieved in the glass. 总 concentration, with similar RO 总 By combining MgO with at least one additional RO species, such as CaO, SrO, and / or BaO, a reduction in dielectric constant and / or loss tangent can be achieved in a glass compared to a glass obtained from a precursor composition having a lower concentration but including a single RO species. 总 Concentration, compared to a glass including a single RO species selected from MgO, CaO, SrO, or BaO, a glass according to the present disclosure comprising a combination of MgO plus CaO, SrO, and / or BaO may have a lower dielectric constant. In another example, for a given RO 总 Concentration, glasses including a combination of MgO plus CaO, SrO, and / or BaO according to the present disclosure may have a lower loss tangent than glasses including a single RO species selected from CaO, SrO, or BaO.

[0148] Without wishing to be bound by theory, it is believed that for glasses obtained from precursor compositions having a single RO species, as the concentration of the single RO species decreases, the dielectric constant and loss tangent of the resulting glass, as measured with a 10 GHz signal, also decrease.

[0149] In some aspects, the amount of alkaline earth oxide in the phase separation glass combined with other materials such as B2O3 and optionally Al2O3 can be selected to provide a phase separation glass with desired characteristics. For example, relative to SiO2 and Al2O3, increasing the amount of alkaline earth oxide can have the effect of reducing the viscosity of the glass melt and can increase melting and forming temperature. Alkaline earth oxide can also increase the CTE and density of glass, and can also affect other properties, such as elastic modulus. Alkaline earth oxide can also reduce liquidus temperature. Therefore, in some aspects, the total amount of alkaline earth oxide B2O3 and Al2O3 can be selected to balance the desired physical properties and formability of the phase separation glass.

[0150] The phase separation glass of the present disclosure may optionally include less than about 2 mol% of the total amount of ZnO, such as in the range of about 0 mol% to about 1.5 mol%, in the range of about 0 mol% to about 1 mol%, or in the range of about 0 mol% to about 0.5 mol%, including all ranges and sub-ranges therebetween. In aspects, the glass may include ZnO in the range of about 0.5 mol% to about 2 mol%, in the range of about 1 mol% to about 2 mol%, or in the range of about 1.5 mol% to about 2 mol%, including all ranges and sub-ranges therebetween.

[0151] In some aspects, the total amount of alkaline earth oxides can be selected so that the RO 总 The ratio of (Al2O3+B2O3) is in the range of about 0.2 to about 0.6, in the range of about 0.2 to about 0.5, or in the range of about 0.2 to about 0.4, including all ranges and sub-ranges therebetween. In aspects, the total amount of alkaline earth oxides can be selected so that RO 总 The ratio of :(Al2O3+B2O3) is in the range of about 0.3 to about 0.6, in the range of about 0.4 to about 0.6, or in the range of about 0.5 to about 0.6, including all ranges and sub-ranges therebetween. In some aspects, RO 总 The ratio of: (Al2O3 + B2O3) can be about 0.2, about 0.24, about 0.25, about 0.28, about 0.29, about 0.3, about 0.32, about 0.35, about 0.36, about 0.4, about 0.5, about 0.55, about 0.58, about 0.6, including all ranges and sub-ranges therebetween.

[0152] The phase separated glass of the present disclosure may optionally include one or more fining agents, such as, as non-limiting examples, SnO2, Sb2O3, As2O3, and / or one or more halogen salts, including fluorine, chlorine, or bromine salts. When one or more fining agents are present in the glass, the fining agents may be present in a total amount of less than about 1 mol%. In some aspects, the clarifier can be present in a total amount of about 0.01 mol% to about 1 mol%, for example, in a range of about 0.01 mol% to about 0.9 mol%, in a range of about 0.01 mol% to about 0.8 mol%, in a range of about 0.01 mol% to about 0.7 mol%, in a range of about 0.01 mol% to about 0.6 mol%, in a range of about 0.01 mol% to about 0.5 mol%, in a range of about 0.01 mol% to about 0.4 mol%, in a range of about 0.01 mol% to about 0.3 mol%, in a range of about 0.01 mol% to about 0.2 mol%, in a range of about 0.01 mol% to about 0.1 mol%, including all ranges and sub-ranges therebetween. In various embodiments, the glass may include a total concentration of fining agents in an amount within a range of about 0.01 mol% to about 0.09 mol%, within a range of about 0.01 mol% to about 0.08 mol%, within a range of about 0.01 mol% to about 0.07 mol%, within a range of about 0.01 mol% to about 0.06 mol%, within a range of about 0.01 mol% to about 0.05 mol%, within a range of about 0.01 mol% to about 0.04 mol%, within a range of about 0.01 mol% to about 0.03 mol%, or within a range of about 0.01 mol% to about 0.02 mol%, including all ranges and sub-ranges therebetween. In embodiments, the total concentration of the clarifier may be in the range of about 0.02 mol% to about 0.1 mol%, in the range of about 0.03 mol% to about 0.1 mol%, in the range of about 0.04 mol% to about 0.1 mol%, in the range of about 0.05 mol% to about 0.1 mol%, in the range of about 0.06 mol% to about 0.1 mol%, in the range of about 0.07 mol% to about 0.1 mol%, in the range of about 0.08 mol% to about 0.1 mol%, or in the range of about 0.09 mol% to about 0.1 mol%, including all ranges and sub-ranges therebetween. However, in other embodiments, the clarifier may be present in an amount ranging from about 0.01 mol% to about 0.5 mol%, including all ranges and sub-ranges therebetween.

[0153] When the content of the clarifier in the phase-separated glass is too large, the clarifier may enter the glass structure and affect various glass properties. However, when the content of the clarifier is too low, the phase-separated glass may be difficult to form. According to one aspect of the present disclosure, SnO2 may be included as a clarifier in a total amount in the range of about 0 mol% to about 0.3 mol%. For example, SnO2 may be present in a total amount in the range of about 0 mol% to about 0.3 mol%, in the range of about 0 mol% to about 0.2 mol%, or in the range of about 0 mol% to about 0.1 mol%, including all ranges and sub-ranges therebetween. In a further embodiment, the glass may contain SnO2 in the range of about 0.05 mol% to about 0.3 mol%, in the range of about 0.05 mol% to about 0.2 mol%, or in the range of about 0.05 mol% to about 0.1 mol%, including all ranges and sub-ranges therebetween.

[0154] The phase separated glass may optionally include contaminants or unintended additives, such as TiO2 or ZrO2. These additional materials, when present, are typically present in very low or trace total amounts of less than about 0.5 mol%, such as within the range of 0 to about 0.4 mol%, within the range of 0 to about 0.3 mol%, or within the range of 0 to about 0.2 mol%, or within the range of 0 to about 0.1 mol%, including all ranges and sub-ranges therebetween.

[0155] In some aspects, the phase separation glass of the present disclosure may be substantially free of alkali metals. As used herein, the phrase "substantially free of" is defined to mean that there is only a trace amount of material, in this case, alkali metal oxides, such as no more than about 0.5 mol%, no more than 0.4 mol%, no more than 0.3 mol%, no more than about 0.2 mol%, or no more than about 0.1 mol% of the total amount. Trace alkali metal oxides may exist due to contamination or limitations in manufacturing. As discussed above, in some implementations, the glass of the present disclosure can be prepared without adding alkali metals so that the glass is substantially free of alkali metals in order to reduce the possibility of ion migration during heat treatment of products formed from the glass. In some applications, reducing or minimizing the possibility of ion migration may be very advantageous, for example, when glass is used as a substrate in an electronic device, ion migration may be undesirable.

[0156] In some aspects, the phase separation glass of the present disclosure may include at least one alkali metal oxide (RO), wherein R2O is Li2O, Na2O, and / or K2O. In some aspects, one or more alkali metal oxides may be present individually or in combination in an amount of 0mol% to about 1mol%. In some aspects, one or more alkali metal oxides may be present individually or in combination in an amount of about 0mol% to about 0.9mol%, about 0mol% to about 0.8mol%, about 0mol% to about 0.7mol%, about 0mol% to about 0.6mol%, about 0mol% to about 0.5mol%, about 0mol% to about 0.4mol%, about 0mol% to about 0.3mol%, about 0mol% to about 0.2mol%, or about 0 to about 0.1mol%, including all ranges and sub-ranges therebetween. For example, Na2O can be present in a total amount in the range of about 0 mol% to about 0.05 mol%, in the range of about 0 mol% to about 0.04 mol%, in the range of about 0 mol% to about 0.03 mol%, in the range of about 0 mol% to about 0.02 mol%, or in the range of about 0 mol% to about 0.01 mol%, including all ranges and sub-ranges therebetween. In aspects, the glass can include NaO2 in the range of about 0.005 mol% to about 0.5 mol%, in the range of about 0.01 mol% to about 0.05 mol%, in the range of about 0.02 mol% to about 0.05 mol%, in the range of about 0.03 mol% to about 0.05 mol%, or in the range of about 0.04 mol% to about 0.05 mol%, including all ranges and sub-ranges therebetween. In another embodiment, K2O can be present in a total amount in the range of about 0 mol% to about 2 mol%, in the range of about 0 mol% to about 1 mol%, in the range of about 0 mol% to about 0.5 mol%, including all ranges and sub-ranges therebetween. In aspects, the glass can include K2O in the range of about 0.1 mol% to about 2 mol%, in the range of about 0.2 mol% to about 2 mol%, in the range of about 0.5 mol% to about 2 mol%, in the range of about 1 mol% to about 2 mol%, or in the range of about 1.5 mol% to about 2 mol%, including all ranges and sub-ranges therebetween.

[0157] In some aspects, the phase-separated glasses of the present disclosure may have a dielectric constant D of about 10 or less, as measured using a signal at 10 GHz. k In some implementations, the phase-separated glass may have a dielectric constant D of about 9 or less, about 8 or less, about 7 or less, about 6 or less, or about 5 or less, as measured using a signal at 10 GHz. kIn some implementations, the phase-separated glass can have a dielectric constant D of about 4.5 to about 6, as measured using a signal at 10 GHz. k .

[0158] In some aspects, the phase-separated glass of the present disclosure can have a loss tangent D of about 0.004 or less, such as about 0.003 or less, as measured using a signal at 10 GHz. f In some aspects, the phase-separated glass of the present disclosure can be characterized by a loss tangent of about 0.0029 to about 0.004, as measured using a signal at 10 GHz. Unless otherwise specified, the dielectric property D k and D f Measured on polished, as-made glass samples that were 3" x 3" and less than 1 mm thick. Test frequencies ranged from 2.7 GHz to 50 GHz. Samples were tested with split post dielectric resonators at signal frequencies equal to or less than 10 GHz or with open cavity resonators at signal frequencies greater than 10 GHz. In each case, the dielectric constant and loss tangent were measured as the shift and broadening of the resonance peaks.

[0159] The phase separation glass of the present disclosure may be suitable for PCB applications. The PCB laminate may include an insulating layer laminated to a conductive film, wherein the insulating layer is disposed between the conductive films. The insulating layer preferably has a low dielectric loss of, for example, less than 0.005 at 10 GHz, and sufficient mechanical strength and fracture toughness to allow handling and post-processing in a production environment. The insulating layer should also be able to withstand drilling without damage or cracking and, depending on the application, may be in the range of about 100 to 700 microns thick. In addition, the insulating layer can withstand temperatures up to 260°C for 30 seconds while maintaining dimensional stability. This temperature is typically based on the temperature required for solder reflow in post-processing of PCB boards. Solder paste is typically used to attach electrical components to their contact pads. The assembly may then be exposed to high temperatures (typically 260°C for 30 seconds) to reflow the solder and form permanent solder joints. Therefore, the insulating layer of the PCB should be a low dielectric loss material that is also able to withstand the solder reflow temperatures typically used in PCB processing with little softening or dimensional change.

[0160] It has been observed that during a drawing process, where a phase separated glass is placed under tension, such as in a down draw process, and drawn into, for example, a glass sheet, optical retardation may be induced in the phase separated glass sheet, as evidenced by stresses in the glass sheet as shown by strain range measurements using polarized light. Annealing has been shown to increase the optical retardation. The longer the annealing time, the greater the optical retardation may be.

[0161] Figure 6 , 7, and 8 show (1) strain range images of approximately 3 centimeters (cm) x 3 cm samples (6(a), 7(a), and 8(a)) of phase separated glass plates and (2) scanning electron microscope (SEM) photographs showing the phases of the glass samples ( Figure 6 (b), 7(b), and 8(b)). Figure 6 The samples are as-drawn samples of the glass without subsequent annealing. Figure 7 The sample is the sample after annealing at 720°C for 2 hours. Figure 8 Depicts the second annealing at 720°C for another 2 hours (ie, a total of four hours). Figure 7 Samples. In particular Figure 7 The increased shading of the sample (a) measured over the strain range indicates an increase in optical retardation. Figure 6-8 From the SEM images, the increase in the size of the secondary phase is evident when the sample is annealed.

[0162] Figure 9-12 After annealing at gradually higher temperatures Figure 5 SEM images of samples of phase-separated glass compositions. For example, Fig. 9 The sample was annealed at a temperature of about 745°C for a period of about 12 hours. The features indicating phase separation are very fine and difficult to discern visually. Fig.10 The sample was annealed at about 800°C for about 12 hours. At this point, the two phases of the glass became visually distinct, although they were still small. Fig.11 The sample was annealed at a temperature of about 850°C for a period of about 12 hours. The different phases are clearly visible. Fig.12 The sample was annealed at about 900°C for about 12 hours. Fig.12 The various phases of the glass are easily distinguishable. Figure 6 , 7 , 8, the higher the annealing temperature, the greater the degree of phase separation, as evidenced by the growth of the secondary phase. Fig. 9 The minor phase is barely discernible, while Fig.12 The secondary phase is clearly visible.

[0163] The two-dimensional Fourier transform technique was used to analyze Figure 9-12 Similar images. The sample was etched with a range of different etching times to highlight the spatial distribution of the two phases. Close inspection of the image revealed that the edges of the slower etched material phase were brighter than the faster etched phase, giving a SEM image signal related to the spatial orientation of the phases. The two-dimensional Fourier transform can be described mathematically using the following equation.

[0164]

[0165] Where x and y are the coordinates of the physical structure, f(x,y) is the signal of the physical structure to be analyzed (in this case the intensity of the backscattered SEM image), u and v are the coordinates in the Fourier domain, and F(u,v) is the Fourier transform of the function f(x,y).

[0166] To understand how the Fourier transform can help identify the spatial orientation of phases, some illustrative examples are examined. First, consider the case where the phases are oriented as alternating vertical lines. The two-dimensional Fourier transform consists of a series of peaks in the horizontal direction of the Fourier plane. The spacing between the peaks will provide information about the width of the vertical domains of the phase. The width of the peaks will provide information about the variation in the width of the vertical domains. A similar response would be expected if the phases were arranged along alternating horizontal lines, except that the peaks in the Fourier transform would be in the vertical direction rather than the horizontal direction. In both cases, the amplitude of the peaks in the Fourier domain will provide information about how many domains have a particular orientation.

[0167] If the material phases are randomly oriented vertically, horizontally, and at every azimuthal angle to the physical plane, but with nearly constant width, the Fourier transform will consist of a ring where the position of the peak in the Fourier domain is inversely proportional to the width of the phase domain. The width of the peak will provide information about the distribution of the phase domain widths.

[0168] Can be used Fig.13 The SEM image is described using the coordinate system shown in . The drawing direction (indicated by arrow 56 in the figure) extends along the y-axis (in the -y direction), the thickness of the glass sheet is in the z-direction, and the x-direction is orthogonal to each of the drawing direction and the thickness direction. If the surface perpendicular to the surface from which the sample was taken is parallel to the x-direction, the sample is referred to as an x-cross-sectional image.

[0169] The two-dimensional Fourier transform (2DFT) corresponding to the sample measured from the x-surface is Fig.14 The light halo around the central point is an annular ring corresponding to the characteristic width of the phase separation feature (i.e., the secondary phase). The uniformity of its radius and width indicates that the structure of this two-dimensional cross-section is nearly isotropic. However, it is slightly easier to see the inhomogeneities if the figure is plotted in rθ space instead of uv space, where

[0170] The data of the samples of the three surfaces plotted in this rθ coordinate system are presented in grayscale form. Fig.15 The vertical axis is the azimuthal direction, θ. The horizontal dimension is the radial direction in the xy Fourier plane, r. The results show that the structures of the two phases are isotropic in the azimuthal direction (vertical axis), but the 31 μm -1The spatial frequencies of the phases indicate that the width of the phase is nearly uniform, with a width of about 32 nm. While the 2DFT cross-section of the x-sample exhibits little anisotropy, the samples at the y- and z-surfaces (with the surface normal along the draw direction and through the thickness, respectively) exhibit larger azimuthal variations, as well as broader variations in the peak widths, suggesting that the material phase domains are being compressed (higher spatial frequencies indicate smaller domain widths). These results suggest that the anisotropy of the spatial distribution of the material phase of a phase-separated material can vary, depending on the orientation of the material relative to the draw direction and through the thickness, but not perpendicular to those directions - that is, within a glass sheet, but perpendicular to the draw direction, shows less anisotropy.

[0171] Unlike other glasses that can be treated after forming to induce phase separation (e.g., by heat treating the glass), it is believed that the phase separated glasses of the present disclosure undergo phase separation by spontaneous spinodal decomposition as the molten glass flows through the downstream glass manufacturing equipment 30 (e.g., as the molten glass passes through various connecting pipes and vessels downstream of the melting vessel and before the forming body). The effect of pulling the molten glass from the forming body on the phase orientation supports this view. That is, phase separation must have occurred before the drawing tension can affect the phase orientation.

[0172] Fig.16 is a schematic diagram of the sample locations used to collect stress measurements, and Fig.17 It is shown that as the glass composition changes from commercially available non-phase-separated glass (i.e. Eagle TM ) to a phase-separated glass composition. This transition took about a month. This transition was achieved by slowly changing the glass composition and trying to maintain a constant glass density. Fig.16 ) Stress data were collected at 140 °C for 15 minutes. The data showed a gradual change in stress (pounds per square inch, psi), from almost no difference in stress at the beginning of the transition (e.g., around day 3) (as expected for commercial glass), to stresses exceeding + / -250 psi at the completion of the transition, to stresses as high as + / -300 psi at day 45.

[0173] Fig.18 It is shown in Eagle TM During the transition from glass to phase separation glass, at various locations on the glass sheet (reference Fig.17 ), the log of stress (in psi) as a function of time 10 To plot the loss tangent D fThe data show that the stress causing the intrinsic birefringence increases while the loss tangent decreases (eg, from about 0.0065 to about 0.0045).

[0174] Fig.19 is during the transition, at several locations on the board (ref. Fig.17 ), a graph of the ratio (B2O3+MgO) / CaO (when the individual components are expressed in mole %) plotted against stress (in psi), showing how the dielectric properties vary with composition.

[0175] The main glass phase of the phase separation glass disclosed herein is rich in SiO2, while the secondary phase is rich in boron (e.g., B2O3). As described above, the greater the amount of SiO2 in the phase separation glass, the greater the component of the electronic circuit (e.g., dielectric constant D k , and loss tangent D f ) more favorable. That is, the dielectric constant and / or loss tangent can be reduced by increasing the amount of SiO2. However, increasing the amount of SiO2 in the glass makes the glass less susceptible to being formed by conventional sheet forming methods (e.g., melt-draw processes). On the other hand, since the primary form of such electronic (e.g., dielectric) components in PCBs is in thin sheets, mass production methods can advantageously reduce costs. Therefore, a method of modifying the composition of a phase-separated intermediate glass sheet is described, wherein the content of SiO2 in the glass sheet may be greatly increased after the glass sheet is formed. Therefore, a mass production method can be used to form the intermediate glass sheet, which can then be further processed to produce a SiO2-rich glass product having desired dielectric properties.

[0176] According to the present disclosure, the phase separated glass article can be etched with a suitable etchant to remove substantially all of the boron-rich secondary phase while leaving behind a silica-rich porous glass article comprising a silica-rich primary phase. In some embodiments, the porous glass article can then be heated to consolidate the porous glass article into a silica-rich solid glass article, such as a glass sheet.

[0177] Thus, a method is described that includes a first step of forming a glass sheet that includes a phase separated glass including at least a first phase and a second phase, such as a phase separated glass as described herein. The phase separated glass sheet may include a width greater than about 340 mm and a length greater than about 440 mm, a width greater than about 680 mm and a length greater than about 880 mm, or a width greater than about 1500 mm and a length greater than about 1500 mm, although smaller or larger sizes are contemplated and possible using, for example, a fusion down-draw process such as the fusion down-draw process described herein.

[0178] The phase-separated glass sheet may have a first phase rich in SiO2 and a second phase rich in B2O3. The phase-separated glass sheet may be optionally cleaned before subsequent steps. For example, the phase-separated glass may be cleaned with a detergent. An ultrasonic bath may be used for cleaning. For example, the phase-separated glass may be cleaned by immersing the phase-separated glass in an ultrasonic bath containing a detergent (e.g., an aqueous solution containing 4 wt% Semiclean) for a period of about 2 minutes to about 6 minutes, such as about 4 minutes.

[0179] In a second step, the phase-separated glass sheet can be exposed to an etchant, such as an acid suitable for etching the second phase from the glass sheet. The acid can be an aqueous solution containing an inorganic acid or an organic acid. Depending on the selected acid and the amount of the secondary phase to be removed, the acid can be present in the solution in an amount of about 5wt% to about 40wt%. Suitable inorganic acids can include at least one of HCl, H2SO4, HNO3, HF, or H3PO4. Exemplary organic acids can include citric acid and / or acetic acid. The etchant can be at a temperature in the range of about 60°C to about 100°C, and the exposure time is in the range of about 1 hour to about 6 hours, for example, in the range of about 2 hours to about 4 hours. The strength of the acid solution and the temperature of the etchant determine the length of time suitable for etching away the second phase rich in boron from the phase-separated glass sheet. Removing the second phase from the phase-separated glass sheet produces a porous glass sheet that mainly or completely contains the first phase, for example, a phase rich in SiO2. The calculated open porosity of the porous glass sheet can be greater than about 28%. During the test, about 8.7% of the pores had a diameter greater than about 3 nm, meaning that the majority of the pores had a diameter less than about 3 nm. The median (d50) pore size of the pores of the porous glass plate can be less than about 1 μm, such as less than about 0.5 μm, less than about 0.1 μm, less than about 0.05 μm, less than about 0.025 μm, or less than about 0.02 μm. Porosity is measured directly by using mercury to intrude the pores. However, this technique is limited to pore sizes exceeding 3 nm. Therefore, porosity is calculated based on density.

[0180] In an optional subsequent step after etching, the resulting porous glass article may be rinsed with deionized water (eg, 18 megohm (Mohm) deionized water).

[0181] The porous glass article obtained by the above-mentioned etching process can also be used for other purposes in addition to being used for electronic applications.For example, because the secondary phase is interconnected, the hole left by etching may be very small (for example, for example, less than about 100nm, less than about 75nm, less than about 50nm, less than about 25nm or for example as small as about 3 nanometer diameters) and can extend through the thickness of the porous glass plate.Therefore, the porous glass plate can be used for multiple applications such as nanofiltration, reverse osmosis and water treatment applications.Although the porous glass plate has a porous structure, the porous glass plate still remains transparent.The surface of the hole can be processed (for example, coated) so that the porous article can be used for microreactor (for example, nanoreactor) application (wherein chemical reaction can be carried out on a very small scale).The pore surface can be coated with a catalyst.In some embodiments, the hole can be impregnated with nano-sized particles to provide additional functions.

[0182] In the third step of the method, the porous glass article can be consolidated by heating the porous glass article to a suitable consolidation temperature. By consolidating the porous glass plate, water molecules can be prevented from entering the pores, thereby stabilizing the performance of the glass plate. Since water is a highly polarized molecule, the moisture in the glass will have an adverse effect on the dielectric properties of the glass. In an embodiment, the porous glass article can be preheated to a temperature in the range of about 100°C to about 300°C for a time in the range of about 1 hour to about 2 hours, so as to dry the porous glass article before consolidation. The dried porous glass article can be further heated to a temperature in the range of about 500°C to about 700°C, such as a temperature in the range of about 550°C to about 650°C, to remove (burn off) any organic contaminants that may contaminate the porous glass article, such as carbon. Contaminants include oil or other environmental pollutants generated during the process. The dried porous glass article can be heated for a time in the range of about 30 minutes to about 2 hours, and a time in the range of about 45 minutes to about 75 minutes.

[0183] To consolidate the porous glass article, the porous glass article may be heated to a consolidation temperature in the range of about 850° C. to about 1250° C., for example, in the range of about 900° C. to about 1250° C., for example, in the range of about 920° C. to about 1250° C., in the range of about 940° C. to about 1250° C., in the range of about 960° C. to about 1250° C., in the range of about 980° C. to about 1250° C., in the range of about 1000° C. to about 1250° C., in the range of about 1020° C. to about 1250° C., or in the range of about 1040° C. to about 1250° C. In some embodiments, the consolidation temperature is in the range of about 0°C to about 1250°C, in the range of about 1060°C to about 1250°C, in the range of about 1080°C to about 1250°C, in the range of about 1100°C to about 1250°C, in the range of about 1120°C to about 1250°C, in the range of about 1140°C to about 1250°C, in the range of about 1160°C to about 1250°C, in the range of about 1180°C to about 1250°C, or in the range of about 1200°C to about 1250°C, including all ranges and sub-ranges therebetween. The consolidation temperature may be, for example, in the range of about 900°C to about 1100°C. The porous glass article may be heated to the consolidation temperature for a time in the range of about 1 hour to about 4 hours, but longer consolidation times are contemplated, such as in the range of about 1 hour to about 24 hours, in the range of about 1 hour to about 20 hours, in the range of about 1 hour to about 16 hours, in the range of about 1 hour to about 12 hours, or in the range of about 1 hour to about 8 hours, including all ranges and sub-ranges therebetween. When heated to the consolidation temperature, the pores in the porous glass article close and the glass becomes solid. SEM and time-of-flight (ToF) secondary ion mass spectrometry (SIM) analysis showed that the porous glass remaining after the etching process is mainly composed of SiO2 (see Table 2). Dielectric property measurements show that once the porous glass is consolidated, D k and D f The values ​​are comparable to those of high purity fused silica (HPFS). However, unlike pure fused silica, phase separated glass can be drawn into large glass sheets, for example, by a fusion down-draw process, then etched and finally consolidated to produce high silica glass sheets with pure fused silica-like dielectric properties.

[0184] Table 1 lists phase separation glass samples (GS17, see Table 5) etched using an acidic aqueous solution containing 5 wt% HQ according to the above etching process. All samples were 2" x 2" coupons of GS17 (see Table 5), cleaned in an ultrasonic bath at 65°C for 2 minutes with a 4% Semiclean detergent solution, and then dried in an oven at 110°C for 1 hour (except for Test C, which was not dried). All etching was performed in a 5 wt% HCl solution at 95°C. For reference, the glass before etching had a D of 4.6 k and D of 0.0037 fTable 1 lists the test names (A-DD), the first heat treatment (1st HT) is expressed as temperature (Tp, °C) / time (Tm, hours), the second heat treatment (2nd HT) is expressed as temperature (Tp, °C) / time (Tm, hours), the first consolidation (1st Con.) is expressed as temperature (Tp, °C) / time (Tm, hours), the second consolidation (2nd Con.) is expressed as temperature (Tp, °C) / time (Tm, hours), the surface treatment using hydrofluoric acid (HF) is expressed as "before heat treatment" (B) or "after final consolidation" (A), the environmental immersion in an 85°C / 85% relative humidity environment is expressed in time (hours), and the dielectric properties dielectric constant D k , and loss tangent D f . Dielectric constants and loss tangents, except those with an asterisk, were measured at 10 GHz. Dielectric properties including asterisks were measured at 5 GHz. Samples containing a prime (') after the dielectric property indicate that the sample was exposed to the laboratory environment (72°C, 20% RH) for approximately 24 hours before the dielectric property was measured. The samples were exposed to the laboratory environment for about 60 hours before the dielectric properties were measured.

[0185] The glass of Test DD had its dielectric properties measured first after consolidation and second after immersion in 85°C / 85% RH. Double dashes indicate that a process step was not performed. Thus, for example, the sample of Test AC was etched before dielectric properties were measured, but was not heat treated, consolidated, subjected to HF, or exposed to an 85°C / 85% RH environment. When comparing the glass samples of Test AC to the glass samples of Test D, which, for example, was only heated to a temperature of 200°C for 1 hour (1 hr.) after etching without benefiting from further heating, the data shows that dielectric properties D k and D f The reduction in dielectric properties is believed to be caused by the removal of water in the porous sample obtained after etching. Similarly, the dielectric properties of the glass sample of Test E are further reduced by the inclusion of a consolidation step, in which the sample is subjected to a temperature of 820°C for 1 hour. Similar results can be observed for other samples, in which further heating through one or more heat treatment steps or one or more consolidation steps may lead to a reduction in dielectric properties. The glass sample of Test DD is represented by two lines because the sample is compared with D after etching and consolidation (including HF treatment of the porous glass article before consolidation). k and D f The measurement was then taken a second time after the consolidated glass article was exposed to an 85°C / 85% RH environment for 24 hours. k and D fThe values ​​of are very consistent before and after 85°C / 85% RH exposure, demonstrating stable dielectric properties even in the presence of moisture.

[0186] Table 1

[0187]

[0188]

[0189] Table 2 lists the composition of melt-formed GS17 glass samples before and after etching in 5wt% HCl at 95°C. ToF SIMS was used for composition analysis to more accurately assess the glass composition remaining after HCl etching. The analysis was performed over the entire thickness of the sample at a field of view of 500 microns x 500 microns. The previous composition components reflect the total amount (including both phases of the phase-separated glass sample). The amounts of all components are expressed in mol%. The data show that after removing most of the boron-rich secondary phase from the sample, the proportion of SiO2 increases significantly, resulting in a nearly pure SiO2 plate that is impossible to form by a melt-draw process. There is no indication of a composition gradient. It is expected that other phase-separated glass compositions described herein will provide similar post-etching results.

[0190] Table 2

[0191]

[0192]

[0193] Tables 3-9 below show exemplary phase separated glasses according to the present disclosure in mole percent (mol%), calculated on an oxide basis from the as-batch glass (the glass precursor composition from which the glass is derived). The glass samples were batch drawn into glass ribbons in a production fusion drawing apparatus and then divided into glass sheets having dimensions of 1500 millimeters (mm) x 1850 mm. The glass sheets were 0.7 mm thick.

[0194] Table 3

[0195]

[0196]

[0197] Table 4

[0198] Glass samples GS9 GS10 GS11 GS12 GS13 GS14 GS15 GS16 <![CDATA[SiO2]]> 68.63 68.72 68.76 68.85 68.91 68.81 68.88 68.75 <![CDATA[Al2O3]]> 8.26 8.14 8.05 7.9 7.84 7.83 7.7 7.63 <![CDATA[B2O3]]> 12.66 12.95 13.19 13.42 13.52 13.68 13.8 14.02 <![CDATA[K2O]]> 0 0 0 0 0 0 0 0 <![CDATA[Na2O]]> 0.03 0.03 0.03 0.03 0.03 0.03 0.03 0.03 MgO 4.54 4.4 4.48 4.84 5.06 5.19 5.43 5.57 CaO 5.62 5.53 5.27 4.78 4.48 4.29 4.01 3.85 SrO 0.14 0.11 0.09 0.06 0.04 0.04 0.03 0.02 BaO 0 0 0 0 0 0 0 0 <![CDATA[SnO2]]> 0.08 0.08 0.08 0.08 0.08 0.08 0.08 0.08 <![CDATA[Fe2O3]]> 0 0 0 0 0 0 0 0 <![CDATA[TiO2]]> 0.01 0.01 0.01 0.01 0.01 0.01 0.01 0.01 ZnO 0 0 0 0 0 0 0 0 <![CDATA[ZrO2]]> 0.03 0.03 0.03 0.03 0.03 0.03 0.04 0.04 <![CDATA[La2O3]]> 0 0 0 0 0 0 0 0 <![CDATA[Y2O3]]> 0 0 0 0 0 0 0 0 <![CDATA[Li2O]]> 0 0 0 0 0 0 0 0 Dk@10GHz Df@10GHz

[0199] Table 5

[0200]

[0201]

[0202] Table 6

[0203]

[0204]

[0205] Table 7

[0206]

[0207]

[0208] Table 8

[0209]

[0210]

[0211] Table 9

[0212]

[0213]

[0214] In order to obtain a low dielectric constant (D k ) and dielectric loss tangent (D f ) and to improve the durability of the glass, several different oxides were studied. Tables 10 and 11 list the composition and measured D of the glass with added ZnO. k and D f data. Fig. 20 and Fig.21 ZnO is used to replace MgO in GS17. k and D f From the graph, it can be seen that with the addition of ZnO for MgO, Dk increases, and with the addition of ZnO, D f However, when ZnO is added to replace B2O3 in the glass, D k and D f The nature does not seem to have changed. Fig. 22 and Fig.23 In the Fig. 22 and Fig.23 In the figure, the hollow circles are glasses with ZnO replacing B2O3, and it can be seen from the figure that the hollow circles are covered by black circles, while the black circles are the same glasses without ZnO. This shows that D k and D f is affected by the B2O3 content, but not by the ZnO content. These data indicate that ZnO is an important fOr, by reducing the resistivity and potentially increasing the fusibility of the glass, while maintaining the same D k and D f This is related to the B2O3 content in this type of glass. The glass melt resistivity of GS57 with about 4 mol% ZnO is Fig.24 It is shown in Figure 2. Clearly, GS57 has a lower resistivity compared to glass sample GS17. Note that GS57 has no CaO, while GS17 has about 5 mol% CaO. The fact that GS17 exhibits low resistivity in the absence of CaO suggests that ZnO can effectively reduce resistivity, thereby improving fusibility.

[0215] Table 10

[0216]

[0217]

[0218] Table 11

[0219]

[0220]

[0221] Rare earth oxides have been shown to reduce glass D f Table 12 lists the compositions of several glasses with La2O3 or Y2O3 added, and the D k and D f data. Fig. 27 and Fig.28 is the corresponding D in the glass replacing Ba with La as a function of mol% La2O3 k and D f The graph clearly shows that when La2O3 increases at the expense of BaO in the glass, D k Increase and D f However, when La2O3 or Y2O3 is added on top of the glass composition (thus not replacing the specific oxide), D k and D f All increased. Fig. 27 and 28 It is shown that for glasses containing La2O3 and Y2O3, D k and D f The data show that in order to reduce the D f , rare earth oxides should be added to replace one of the larger alkaline earth oxides in the glass.

[0222] Table 12

[0223]

[0224]

[0225] Compared with other metal oxides, transition metals have relatively low polarizabilities, so it is believed that this should lead to the D k and D f Tables 13 and 14 list the compositions of several glasses with different transition metal oxides added, and the D measured at 10 GHz for each of these glasses. k and D f The data show that transition metals (except Co) provide a significant reduction in D in alkaline earth aluminoborosilicate glasses when replacing CaO. k means, such as Fig.29 However, Fig.30 The data shown indicate that transition metals may not reduce the D f But it may cause D f Compared to the parent glass, the increase remains essentially constant. Transition metals can also be used to color the glass.

[0226] Table 13

[0227]

[0228]

[0229] Table 14

[0230]

[0231]

[0232] Fluorine is a halide element used in glass melting to reduce the viscosity of the glass melt and to aid in the clarification of the glass melt. When it replaces B2O3, it can also reduce D f , while maintaining essentially the same D as the base glass k Table 15 shows the three glass compositions and their D k and D f data. Fig.31 and Fig.32 The corresponding D is shown as a function of mol% F- k and D fAs shown, the B2O3 content of glass samples GS95 and GS96 is reduced compared to GS94, and fluorine is added. The data show that for glasses with 4.5 mol% fluorine (F-) replacing B2O3, D k remains basically unchanged, while D f This not only helps to reduce the D f , also helps to reduce the B2O3 content in the glass, thereby reducing melting defects such as silicon knots, and reduces the viscosity of the glass melt, making the glass easier to melt because less energy is required to melt. F- can also help reduce bubbles or seeds caused by insufficient glass fining.

[0233] Table 15

[0234] Glass GS94 GS95 GS96 <![CDATA[SiO2]]> 71.16 70.28 69.68 <![CDATA[Al2O3]]> 5.32 5.20 5.20 <![CDATA[B2O3]]> 19.03 17.77 16.15 <![CDATA[K2O]]> 0 0 0 <![CDATA[Na2O]]> 0 0 0 MgO 3.26 3.24 3.28 CaO 1.15 1.13 1.10 F 0 2.30 4.51 <![CDATA[SnO2]]> 0.09 0.09 0.08 Dk@10GHz 4.09 4.09 Df@10GHz 0.0014 0.0011

[0235] In yet another aspect, conductive vias and optional conductive traces (e.g., lines) can be added to one or more porous intermediate glass articles formed from the phase separated glasses disclosed herein. As used herein, the term "via" refers to a small hole that passes through one or more layers of a circuit board, the via including a conductive material disposed therein that forms an electrical connection between conductive layers (e.g., lines or traces) and / or electrical components on the circuit board. The via can be a through hole, wherein the hole and the conductive material pass through the entire thickness of the circuit board, extending from one major surface of the circuit board to the opposite major surface, or a "blind" via, wherein the via and the conductive material partially pass through the thickness of the circuit board. That is, a blind via terminates inside the body of the circuit board between the exposed, outwardly facing major surfaces.

[0236] In some embodiments, the porous intermediate glass products can be laminated together and co-fired (consolidated together) to form a glass circuit board, the glass circuit board including conductive through holes extending at least partially through the thickness of the glass circuit board. The glass circuit board may also include interconnected electrical paths extending on the surface and / or inside the glass circuit board, for example from one through hole to another through hole. In aspect, once the porous intermediate glass product is obtained from the phase-separated glass plate by etching (leaching) the glass plate according to the method disclosed herein, holes can be formed in the porous intermediate glass product by laser ablation or chemical etching, and then filled with a suitable conductive material to form through holes. Before the acid leaching step, the phase-separated glass has a lower ablation threshold. After the leaching step, the ablation threshold is close to the ablation threshold of molten silica. Therefore, compared with after the leaching step, before the leaching step (for example, before the porous intermediate glass product is obtained), the hole formation can be carried out faster. In an embodiment, holes can be formed by using one of a variety of lasers, using wavelengths from UV to far infrared, and pulse durations from quasi-continuous to ultrafast, both in the phase-separated glass substrate before etching and in the porous intermediate product after etching. The selection of a suitable laser may also depend on the desired hole size. For large through holes with a diameter greater than one hundred or several hundred microns, RF-excited (quasi-continuous wave or nanosecond pulsed) CO2 lasers can be used; for small holes with a diameter of a few microns or tens of microns, ultrafast laser-induced damage can be used, followed by chemical etching.

[0237] The following example demonstrates the use of a direct ablation method to form through holes in a phase-separated glass product after a leaching step. A pulsed 355 nm wavelength Nd:YAG solid-state laser is used to form holes with a diameter of about 400 microns (μm) in a porous glass substrate produced by the process described herein. That is, the spinodal phase-separated glass substrate is exposed to an acid solution to leach to remove the second phase containing B2O3 and produce a porous intermediate glass substrate whose main phase contains more than 95 mol% SiO2. The resulting porous glass substrate is then laser processed to form holes. The laser is operated at a repetition rate of 50 kilohertz (kHz), a pulse energy of 70 microjoules (μJ) and a power of 3.5 watts (W). A galvanometer with a 100 mm focal length (f=100 mm) telecentric lens is used to scan the extended laser beam. The spot size of the laser beam at the focus is about 15 μm. The spot size used in this article refers to the maximum irradiance center of the beam from the beam irradiation surface to 1 / e 2 The radial distance (radius) of the irradiance at a point. The porous intermediate glass substrate is placed on a lift and the laser beam is scanned in a series of concentric circles while the substrate is moved by the lift through the focus of the laser beam. Fig.33 The UV laser-formed holes are shown before and after thermal consolidation. Fig.33, (a) and (c)) show an average pore diameter of about 150 μm, and the right column ( Fig.33 (b) and (d)) show an average pore diameter of about 400 μm. Fig.33 , (a) and (b)), show two pore sizes, 150 μm (left) and 400 μm (right), formed by laser ablation in as-received leached glass. Holes extending completely through the substrate are shown to be formed without visible cracks. The bottom row of images ( Fig.33 , (c) and (d)) show the pore shape of the substrate after thermal consolidation. The size and shape of the pores are basically maintained. Fig.34 The x-ray diffraction patterns on the consolidated substrate are shown. Curve 100 is the diffraction pattern on the glass surface away from the through hole, and curve 102 is the diffraction pattern close to the through hole. Both patterns show completely amorphous characteristics, for example, where a crystalline phase such as cristobalite is not formed after thermal consolidation.

[0238] In an embodiment, the hole can be filled with a conductive ink, such as an ink containing a metal (such as but not limited to copper, silver or platinum) to form an intermediate circuit board. However, since the consolidation temperature is higher than the melting temperature of some metals (such as copper, gold or silver), these metals with "low" melting points may not be suitable for pre-consolidation through-hole filling. Suitable, non-limiting conductive inks for pre-consolidation hole filling can be platinum-based inks (provided by Applied Technologies) with about 85wt% Pt, 5wt% glass and 10wt% organic binder. Other metal-based inks can include (but not limited to) molybdenum-based inks or tungsten-based inks. In addition, conductive paths can be deposited between through holes on the surface of a porous glass substrate. For example, through holes can be filled with conductive inks, and further, the conductive ink can be deposited as a continuous line extending between a through hole and one or more other through holes. The filling and / or deposition of conductive inks can be performed, for example, using a screen printing process. The porous glass substrate containing the conductive ink can be consolidated (fired) to form a glass circuit board.

[0239] In some embodiments, two or more intermediate circuit boards can be stacked and then fired together, the intermediate circuit board comprising a plurality of through holes containing conductive ink, and optionally a conductive ink deposited as a conductive trace (line) from one through hole to one or more other through holes, so that the stacked intermediate product is consolidated into a glass circuit board, the glass circuit board comprising an external and / or internal conductive path arranged on one or more layers of the glass circuit board. The alignment of the two or more intermediate circuit boards during the stacking process can be achieved by edge alignment or by fiducial marks placed on each intermediate circuit board. A thermally conductive substrate such as SiC can be used to clamp the stack. Pressure may be applied to the stack during the consolidation process, for example, by a thermally conductive substrate. In some embodiments, before the intermediate circuit board stack is placed between the thermally conductive substrates, or at least before consolidation, the intermediate circuit board stack can be divided into a plurality of intermediate circuit board stacks, thereby facilitating the simultaneous formation of multiple glass circuit boards. In aspect, some of the plurality of through holes on an intermediate circuit board in the stack can be arranged to align (align) with other through holes of another adjacent intermediate circuit board in the stack, so that after firing, the aligned through holes form a continuous electrical path through the adjacent layers of the resulting glass circuit board.

[0240] By way of example and not limitation, Fig.35 Depicted are a first intermediate circuit board 120 and a second intermediate circuit board 122. The first intermediate circuit board 120 includes a first major surface 124 and a second major surface 126 opposite the first major surface 124. The first major surface 124 can be substantially flat (substantially planar) and parallel to the second major surface 126. Therefore, the second major surface 126 can also be substantially flat (substantially planar).

[0241] Second midplane board 122 includes a third major surface 128 and a fourth major surface 130. Third major surface 128 may be substantially flat (substantially planar) and parallel to fourth major surface 130. Thus, fourth major surface 130 may also be substantially flat (substantially planar).

[0242] The first intermediate circuit board 120 includes a first plurality of through holes 132, such as first through holes 132a, second through holes 132b, and third through holes 132c, each of which includes a hole extending through the thickness of the first intermediate circuit board between the first major surface 124 and the second major surface 126, as described herein. The first intermediate circuit board 120 can have less than three through holes, such as two through holes, or more than three through holes, such as four through holes, five through holes, six through holes, or more than six through holes, such as tens or hundreds of through holes.

[0243] Similarly, second intermediate circuit board 122 includes a second plurality of through holes 134, such as fourth through holes 134a, fifth through holes 134b, and sixth through holes 134c, as described herein, each of fourth, fifth, and sixth through holes 134a, 134b, 134c comprises a hole extending through the thickness of second intermediate circuit board 122 between third major surface 128 and fourth major surface 130. Similar to first intermediate circuit board 120, second intermediate circuit board 122 may have less than three through holes, such as two through holes, or more than three through holes, such as four through holes, five through holes, six through holes, or more than six through holes, such as dozens or hundreds of through holes.

[0244] exist Fig.35 In the example of FIG. 1 , a first line (trace) 136a of conductive material is deposited on the first major surface 124 of the first intermediate circuit board 120 and extends between the first through hole 132a and the second through hole 132b. The first line 136a of conductive material is electrically connected to the first through hole 132a and the second through hole 132b. The second line 136b of conductive material (at Fig.35 The conductive material (shown as a dotted line in FIG. 1 ) is similarly deposited on the second main surface 126 and extends between the second through hole 132b and the third through hole 132c, and the second line 136b of the conductive material is electrically connected to the second through hole 132b and the third through hole 132c. Therefore, the first through hole 132a is electrically connected to the third through hole 132c through the first line 136a of the conductive material and the second line 136b of the conductive material.

[0245] In addition, a third line (trace) 136c of conductive material is deposited on the third major surface 128 of the second intermediate circuit board 122, extending between the fourth through hole 134a and the fifth through hole 134b, and the third line 136c of conductive material is electrically connected to the fourth through hole 134a and the fifth through hole 134b. Fig.35 The conductive material (shown as a dotted line in FIG. 1 ) is similarly deposited on the fourth main surface 130, extending between the fifth through hole 134b and the sixth through hole 134c, and the fourth line 136d of the conductive material is electrically connected to the fifth through hole 134b and the sixth through hole 134c. Therefore, the fourth through hole 134a is electrically connected to the sixth through hole 134c through the third line 136c of the conductive material and the fourth line 136d of the conductive material.

[0246] According to the embodiments disclosed herein, the first intermediate circuit board 120 can be placed in contact with the second intermediate circuit board 122 to form a stack 140 of intermediate circuit boards. For example, the dimensions of the first intermediate circuit board 120 can be the same as the dimensions of the second intermediate circuit board 122, such that the length and width of the first intermediate circuit board 120 are equal to the corresponding length and width of the second intermediate circuit board 122. Therefore, in an embodiment, the first intermediate circuit board 120 can be arranged so that the edge surface of the first intermediate circuit board 120 is substantially coplanar with the corresponding edge surface of the second intermediate circuit board 122. However, similar dimensions are not required. Fig.35 In the example of FIG. 1 , a first intermediate circuit board 120 and a second intermediate circuit board 122 are shown arranged so that (although separated for illustration purposes) the first major surface 124 of the first intermediate circuit board 120 is an exterior (exposed) major surface, and the fourth major surface 130 is an exterior (exposed) major surface. Conversely, the second major surface 126 is arranged opposite the third major surface 128 and is located inside the stack 140 of intermediate circuit boards, and the third major surface 128 is arranged opposite the second major surface 126 and is located inside the stack 140 of intermediate circuit boards. In addition, the first line 136a of the conductive material extending between the first through-hole 132a and the second through-hole 132b on the first major surface 124 is an exterior line of the conductive material, while the second line 136b of the conductive material extending between the second through-hole 132b and the third through-hole 132c is an interior line of the conductive material, i.e., located inside the stack 140. Similarly, the third line 136c of conductive material extending between the fourth through hole 134a and the fifth through hole 134b on the third major surface 128 is an inner line of conductive material, while the fourth line 136d of conductive material extending between the fifth through hole 134b and the sixth through hole 134c is an outer line of conductive material. Therefore, when the first middle circuit board 120 is positioned in contact with the second middle circuit board 122 (or vice versa), the second line 136b of conductive material and the third line 136c of conductive material extend within the inner region of the stack. Fig.35 In the embodiment, the first intermediate circuit board 120 is positioned on and in contact with the second intermediate circuit board 122, so that the third through hole 132c is in contact with or close to the fourth through hole 134a, i.e., aligned with it, so that the longitudinal axis of the third through hole 132c is coaxial with the longitudinal axis of the fourth through hole 134a.

[0247] As mentioned above and Fig.36, a stack 140 of intermediate circuit boards can be arranged between a pair of thermally conductive substrates 141a, 141b and subjected to a heating and consolidation cycle as described herein. In an embodiment, a force can be applied to the stack 140 by the thermally conductive substrates 141a, 141b, as indicated by arrows 143. As a result of the consolidation cycle, the first intermediate circuit board 120 (second major surface 126) is fused to the second intermediate circuit board 122 (third major surface 128) to form a glass circuit board 142 (see Figure 37-38 ), the glass circuit board 142 includes a first outer main surface 144 corresponding to the first main surface 124 of the first intermediate circuit board 120 and a second outer main surface 146 corresponding to the fourth main surface 130 of the second intermediate circuit board 122. In this process, the holes of the porous first intermediate circuit board 120 are closed with the holes of the second intermediate circuit board 122. In addition, the conductive materials constituting the first and second plurality of through holes 132, 134 and the conductive lines extending therebetween are sintered. The aligned through holes (e.g., the third through hole 132c and the fourth through hole 134a) are physically and electrically connected, thereby forming a through hole extending from the first main surface 144 to the second main surface 146 through the total thickness of the glass circuit board 142. In fact, while each through-hole in the first plurality of through-holes 132 and each through-hole in the second plurality of through-holes 134 are through-holes with respect to their respective intermediate circuit boards, once the plurality of intermediate circuit boards are fused by consolidation, some through-holes may extend completely through the total thickness of the glass circuit board, while other through-holes may extend from one major surface of the glass circuit board, such as from the first major surface 144 or the second major surface 146, partially through the total thickness of the glass circuit board instead of through the total thickness, thereby becoming blind through-holes. In the case where the through-holes on each of the plurality of intermediate circuit boards forming the stack 140 are aligned through-holes, the final through-holes formed by the consolidation step produce through-holes.

[0248] A multi-step heat treatment and consolidation cycle may be used to co-fire the porous intermediate product and the conductive ink, as described previously herein, or a heat treatment and consolidation cycle similar thereto may be used. For example, a three-step heat treatment scheme may include: baking the porous glass substrate in an oven at 200°C for 1 hour to remove moisture; heating the baked porous glass substrate at 600°C for 1 hour to remove carbon impurities in the porous glass substrate; consolidating the porous glass substrate and the conductive ink at 960-1100°C for 2 hours to close the pores of the porous glass substrate. After co-firing (consolidation), the resulting substrate remains amorphous.

[0249] It will be apparent to those skilled in the art that various modifications and variations of the embodiments of the present disclosure may be produced without departing from the spirit and scope of the present disclosure. Therefore, it is intended that the present disclosure covers such modifications and variations as long as they fall within the scope of the appended claims and their equivalents.

Claims

1. A method for manufacturing a glass circuit board, comprising: exposing at least one spinodal phase-separated glass substrate comprising a primarily SiO2 first phase and a second phase comprising B2O3 to an acid solution comprising about 5 wt % to about 40 wt % of an acid at a temperature in the range of about 60° C. to about 95° C. for a time in the range of about 8 hours to about 24 hours to remove at least a portion of the second phase from the at least one spinodal phase-separated glass substrate and obtain at least one porous glass substrate comprising a total SiO2 content greater than about 95 mol %; forming a plurality of holes in the at least one porous glass substrate; depositing a conductive material in the plurality of holes to form an intermediate circuit board including a plurality of through-holes; and The intermediate circuit board is consolidated to form the glass circuit board.

2. The method of claim 1, wherein the acid solution comprises at least one of HCl, H2SO4, HNO3, HF, or H3PO4.

3. The method of claim 1, wherein the acid solution comprises HCl.

4. The method of claim 3, wherein the acid solution comprises about 5 wt% HCl.

5. The method of claim 1, wherein the acid solution comprises at least one of citric acid or acetic acid.

6. The method of claim 1, wherein the at least one porous glass substrate has an open porosity greater than about 28%.

7. The method of claim 1, wherein forming the plurality of holes comprises laser ablation or chemical etching.

8. The method of claim 7, wherein forming the plurality of holes comprises using an RF excited CO2 laser.

9. The method of claim 7, wherein forming the plurality of holes comprises using a laser operating at an ultraviolet wavelength.

10. The method of claim 1, before consolidating the intermediate circuit board, further comprising depositing the conductive material on the porous glass substrate as a line between a first through-hole of the plurality of through-holes and a second through-hole of the plurality of through-holes.

11. The method of claim 1, further comprising heat treating the intermediate circuit board at a temperature in a range of about 500°C to about 700°C for a time in a range of about 45 minutes to about 75 minutes.

12. The method of claim 1, wherein the consolidating comprises heating the intermediate circuit board to a consolidation temperature in a range of about 850°C to about 1250°C for a time in a range of about 1 hour to about 24 hours.

13. The method of claim 1, wherein the at least one spinodal phase separation glass substrate comprises a plurality of spinodal phase separation glass substrates, the exposing produces a plurality of porous glass substrates, and wherein: forming the plurality of pores comprises forming pores in at least a subset of the plurality of porous glass substrates, The depositing comprises depositing the conductive material in at least the subset of pores of the porous glass substrate to obtain a plurality of intermediate circuit boards, arranging the plurality of intermediate circuit boards to form a stack of intermediate circuit boards, and Wherein said consolidating comprises consolidating a stack of intermediate circuit boards to form said glass circuit board.

14. The method of claim 13, wherein prior to said consolidating, the stack of intermediate circuit boards is positioned between a pair of thermally conductive substrates.

15. The method of claim 14, wherein the pair of thermally conductive substrates comprises SiC.

16. The method of claim 1, wherein the glass circuit board is oxide-based and comprises: greater than about 95 mol% SiO2; Less than about 1 mol% Al2O3; Less than about 3 mol % B2O3.

17. The method of claim 1, wherein the glass circuit board comprises less than 0.5 mol% in total of one or more alkaline earth oxides (RO), wherein RO is at least one of MgO, CaO, SrO, or BaO.

18. The method of claim 1, wherein the dielectric constant D of the glass circuit board is k Less than about 6.0 when measured at 10 GHz.

19. The method of claim 18, wherein D k Less than about 4.0 when measured at 10 GHz.

20. The method of claim 1, wherein the at least one glass circuit board has a loss tangent D f Less than about 0.001 when measured at 30 GHz.

21. The method of claim 20, wherein D f Less than about 0.001 when measured at 10 GHz.

22. The method of claim 1, wherein the spinodal phase separation glass substrate comprises: From about 59 mol% to about 69 mol% of the total amount of SiO2; About 3 mol % to about 13 mol % of the total amount of Al2O3; From about 9.8 mol % to about 20 mol % of the total amount of B2O3; and One or more alkaline earth oxides (RO) totaling about 3.9 mol % to about 11.5 mol %, wherein RO is selected from the group consisting of MgO, CaO, SrO, and BaO.

23. The method of claim 22, wherein B2O3 / (Al2O3+SiO2) is in the range of about 0.12 to about 0.

3.

24. The method of claim 22, wherein the spinodal phase separation glass substrate comprises SiO2 in a range of about 68.0 mol% to about 69.0 mol%.

25. The method of claim 1, wherein the spinodal phase separation glass substrate is oxide-based and comprises: About 57 mol% to about 70 mol% of the total amount of SiO2 About 4.7 mol% to about 10.5 mol% of the total amount of Al2O3 About 11.2 mol% to about 15.2 mol% of the total amount of B2O3 From about 1.2 mol% to about 7.4 mol% total amount of ZnO; and One or more alkaline earth oxides (RO) totaling about 3.7 mol % to about 20 mol %, wherein RO is selected from the group consisting of MgO, CaO, SrO, and BaO.

26. The method of claim 25, wherein the spinodal phase separation glass substrate comprises SnO in a range of about 0.09 mol% to about 0.15 mol%.

27. The method of claim 25, wherein the spinodal phase separation glass substrate comprises MgO in a range of about 1.5 mol% to about 9.6 mol%.

28. The method of claim 27, wherein MgO / ZnO is in the range of about 0 to about 3.

7.

29. The method of claim 27, wherein B2O3 / ZnO is in the range of about 1.6 to about 12.

6.

30. The method of claim 1, wherein after said consolidating, said glass circuit board comprises amorphous glass.

31. A glass circuit board, comprising: greater than about 95 mol% SiO2; Less than about 1 mol% Al2O3; Less than about 3 mol% B2O3; a plurality of holes disposed in the glass circuit board; and The dielectric constant D of the glass circuit board k Less than about 6.0 when measured at 10 GHz.

32. The glass circuit board of claim 31 , wherein the plurality of through holes include a first through hole and a second through hole, and a conductive material is disposed on the glass circuit board as a line extending between the first through hole and the second through hole such that the conductive material forms an electrical path between the first through hole and the second through hole.

33. A glass circuit board as described in claim 31, wherein the glass circuit board includes a first major surface and a second major surface opposite to the first major surface, the plurality of through holes include a first through hole extending partially through the thickness of the glass circuit board from the first major surface and a second through hole extending partially through the thickness of the glass circuit board from the second major surface, and the conductive material forms an electrical path between the first through hole and the second through hole.

34. The glass circuit board of claim 31, wherein the electrical path is located inside the glass circuit board.

35. The glass circuit board of claim 31, wherein the plurality of through-holes includes a third through-hole, and the electrical path is in electrical communication with the third through-hole.

36. The glass circuit board of claim 31, wherein the plurality of through holes include at least one blind through hole.

37. The glass circuit board according to claim 31, wherein the loss tangent D of the glass circuit board is f Less than about 0.001 when measured at 30 GHz.

38. The glass circuit board as claimed in claim 37, wherein D f Equal to or less than about 0.0005 when measured at 10 GHz.

39. The glass circuit board of claim 31, wherein the glass circuit board comprises amorphous SiO2.

40. A method for manufacturing a glass circuit board, comprising: forming a plurality of holes in at least one spinodal phase separation glass substrate, the glass substrate comprising a first major surface, a second major surface opposite the first major surface, and a thickness therebetween, the at least one spinodal phase separation glass substrate further comprising a primarily SiO2 first phase and a second phase comprising B2O3, and wherein each hole of the plurality of holes extends through the thickness of the spinodal phase separation glass substrate; exposing the at least one spinodal phase separation glass substrate to an acid solution comprising about 5 wt % to about 40 wt % of an acid at a temperature in a range of about 60° C. to about 95° C. for a time in a range of about 8 hours to about 24 hours to remove at least a portion of the second phase from the at least one spinodal phase separation glass substrate, and wherein after the exposure, the total SiO2 content of the spinodal phase separation glass substrate is greater than about 95 mol%; depositing a conductive material in the plurality of holes to form an intermediate circuit board including a plurality of through-holes; and The intermediate circuit board is consolidated to form the glass circuit board.

41. The method of claim 40, wherein the acid solution comprises at least one of HCl, H2SO4, HNO3, HF, or H3PO4.

42. The method of claim 40, wherein the acid solution comprises HCl.

43. The method of claim 42, wherein the acid solution comprises about 5 wt% HCl.

44. The method of claim 40, wherein the acid solution comprises at least one of citric acid or acetic acid.

45. The method of claim 40, wherein after said exposing, said at least one spinodal phase separated glass substrate has an open porosity greater than about 28%.

46. ​​The method of claim 40, wherein forming the plurality of holes comprises laser ablation or chemical etching.

47. The method of claim 46, wherein forming the plurality of holes comprises using an RF excited CO2 laser.

48. The method of claim 46, wherein forming the plurality of holes comprises using a laser operating at an ultraviolet wavelength.

49. The method of claim 40, wherein depositing the conductive material comprises previously depositing the conductive material as a line between a first via of the plurality of vias and a second via of the plurality of vias.

50. The method of claim 49, wherein depositing the conductive material as a line is performed prior to consolidating the intermediate circuit board.

51. The method of claim 40, further comprising heat treating the intermediate circuit board at a temperature in a range of about 500°C to about 700°C for a time in a range of about 45 minutes to about 75 minutes.

52. The method of claim 40, wherein the consolidating comprises heating the intermediate circuit board to a consolidation temperature in a range of about 850°C to about 1250°C for a time in a range of about 1 hour to about 24 hours.

53. A method as claimed in claim 40, wherein the at least one spinodal phase separation glass substrate comprises a plurality of spinodal phase separation glass substrates, the method further comprising forming the plurality of holes in at least a subset of the plurality of spinodal phase separation glass substrates, depositing the conductive material in the plurality of holes of at least the subset of the spinodal phase separation glass substrates to obtain a plurality of intermediate circuit boards, arranging the plurality of intermediate circuit boards to form a stack of intermediate circuit boards, and wherein the consolidation comprises consolidating the stack of intermediate circuit boards to form the glass circuit board.

54. The method of claim 53, wherein prior to said consolidating, the stack of intermediate circuit boards is positioned between a pair of thermally conductive substrates.

55. The method of claim 54, wherein the pair of thermally conductive substrates comprises SiC.

56. The method of claim 40, further comprising delivering molten material to a forming body, drawing a glass ribbon from the forming body, and separating the spinodal phase separated glass substrate from the glass ribbon.

57. The method of claim 56, wherein the molten material comprises a 35,000 poise temperature greater than about 1250°C.

Citation Information

Cited By

  • Zirconite composite material resistant to high-alkali glass erosion and preparation method thereof

    CN119841639A

  • Zircon composite material resistant to high-alkali glass corrosion and preparation method thereof

    CN119841639B